W-Pt-Cu ALLOY

JP2025024187AActive Publication Date: 2025-02-19NORITAKE MACHINE TECHNO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024203150
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-19
Estimated Expiration
2040-09-30

AI Technical Summary

Benefits of technology

【0008】 本発明者は、タングステン部材と異種金属部材とを接合する新規な技術を見出すために種々の実験と検討を行った結果、W部材用の接合材として好適に機能する新規な合金材料を発見した。具体的には、PtとWを含む合金(Pt-W合金)と、銅(Cu)を含むCu源とを接触させた状態で加熱処理を行うと、驚くべきことに、Pt-W合金のPtがCuに移動することを発見した。そして、このCuによるPtの吸収は、CuがPt-W合金の結晶粒界に入り込みながら進むため、Wを主成分とするW相と、PtとCuとを含むPt-Cu相とが混在した三元二相の合金材料(以下「W-Pt-Cu合金」ともいう)が生成された。一般的には、WとCuは互いに混合して合金を形成することはないと考えられており、このような合金は過去に報告されていなかった。本発明者らは、このW-Pt-Cu合金は、Cuをはじめとする異種金属部材とW部材とを良好に接合する新規な接合材になり得ると考え、当該合金材料の性質と生成メカニズムを解析した。その結果、上記W-Pt-Cu合金は、以下に示すメカニズムによって生成されることを見出した。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024187000001_ABST
    Figure 2025024187000001_ABST
Patent Text Reader

Abstract

To provide a new technique which achieves a suitable joint between a tungsten member and a dissimilar metal member.SOLUTION: A manufacturing method moves platinum (Pt) in a Pt-W alloy containing the platinum (Pt) and tungsten (W) to a Cu source containing copper (Cu). The manufacturing method can manufacture an alloy material 10 in which a W phase 12 containing W as a main component, and a Pt-Cu phase 14 containing a Pt-Cu alloy as a main component are mixed. The alloy material 10 exhibits suitable joinability to a tungsten member because an interface between the W phase 12 and the Pt-Cu phase 14 is stable. The alloy material 10 contains the Pt-Cu phase 14, and accordingly also exhibits suitable joinability to a dissimilar metal member. Specifically, the alloy material is usable as a new joint material for achieving a suitable joint between the tungsten member and the dissimilar metal member.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alloy material, for example, an alloy material that can be used as a joining material for joining a tungsten member and a metal member other than tungsten. [Background technology]

[0002] Tungsten members containing tungsten (W) (hereinafter also referred to as "W members") have the characteristics of a high melting point and a low thermal expansion coefficient, and are highly reliable in high-temperature environments. For this reason, W members are used in ultra-high-temperature parts exposed to high-temperature environments, such as divertors, accelerators, plasma discharge devices, high-temperature furnaces, and thin-film formation devices. On the other hand, tungsten is a rare and expensive metal, and is difficult to process, so it is often used in a state where it is joined with metal members other than tungsten (hereinafter also referred to as "dissimilar metal members"). For example, from the viewpoint of material cost and heat dissipation (thermal conductivity), copper (Cu) is used as the dissimilar metal member to be joined.

[0003] For example, brazing material containing silver (Ag) or copper is used to join the W member and the dissimilar metal member. An example of such brazing material is disclosed in Patent Documents 1 and 2. Specifically, Patent Document 1 discloses a technique of using a brazing material containing silver (Ag), copper (Cu), zinc (Zn) and cobalt (Co) in joining cemented carbide made by sintering tungsten carbide (WC) using cobalt (Co). This suppresses the diffusion of Co in the cemented carbide into the brazing material, and prevents damage due to a decrease in the strength of the cemented carbide. Meanwhile, Patent Document 2 uses a brazing material containing phosphorus (P) when joining alumina dispersion strengthened copper and a joined metal (for example, tungsten). The heat treatment temperature during joining is set to a range lower than the melting point of copper and higher than the melting point of copper lowered by the eutectic reaction between phosphorus and copper. This joins the alumina dispersion strengthened copper and the joined metal.

[0004] Another joining method other than brazing is the NDB method (Non Defective Bonding). The NDB method is a technique for directly joining a W member and a dissimilar metal member, and examples of the method are disclosed in Non-Patent Documents 1 and 2. For example, in Non-Patent Document 1, a tungsten member and a copper member are melted and cooled while being in contact with each other. Non-Patent Document 1 predicts that by carrying out such joining method, the molten copper member will penetrate into the minute uneven surface of the W member, and the mutual attraction between atoms will increase, forming a pseudo metallic bond. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5385951 [Patent Document 2] Patent No. 6528257 [Non-patent literature]

[0006] [Non-Patent Document 1] J.Plasama Fusion Res. Vol.95, No.8(2019)374-376 [Non-Patent Document 2] Journal of Smart Processing, Vol. 6, No. 5 (September 2017) Summary of the Invention [Problem to be solved by the invention]

[0007] However, with the recent expansion of the use of W members, a new technique is required to more suitably bond W members and dissimilar metal members. The present invention has been made in response to such a demand, and its main purpose is to provide a new technique to realize a suitable bond between tungsten members and dissimilar metal members. [Means for solving the problem]

[0008] The present inventors conducted various experiments and studies to find a new technology for joining tungsten members and dissimilar metal members, and discovered a new alloy material that functions well as a joining material for W members. Specifically, the inventors discovered that when an alloy containing Pt and W (Pt-W alloy) is heated in contact with a Cu source containing copper (Cu), Pt in the Pt-W alloy is surprisingly transferred to Cu. The absorption of Pt by Cu proceeds while Cu penetrates into the grain boundaries of the Pt-W alloy, so that a ternary two-phase alloy material (hereinafter also referred to as "W-Pt-Cu alloy") is generated in which a W phase containing W as the main component and a Pt-Cu phase containing Pt and Cu are mixed. It is generally believed that W and Cu do not mix with each other to form an alloy, and such an alloy has not been reported in the past. The inventors of the present invention believed that this W-Pt-Cu alloy could be a new joining material that can effectively join dissimilar metal members such as Cu to W members, and analyzed the properties and formation mechanism of the alloy material. As a result, they found that the W-Pt-Cu alloy is formed by the following mechanism.

[0009] First, the Pt-W alloy, which is a precursor of the W-Pt-Cu alloy, is an alloy containing Pt and W, as described above. Since the Pt-Cu alloy is more stable than the Pt-W alloy, it is believed that the migration of Pt in the Pt-W alloy to Cu progressed as a result of contacting the Pt-W alloy with the Cu source. It is also believed that the interface between the W phase, which is mainly composed of W, and the Pt-Cu phase, which contains Pt and Cu, is more stable than the interface between the Pt-W alloy and Cu. Here, when looking at the bonding with the tungsten member, the stability of the interface between the W phase and the Pt-Cu phase leads to the stability of the bonding between the tungsten member and the alloy material. This is because the tungsten member is mainly bonded to the Pt-Cu phase at the bonding surface. In this way, by preparing a Pt-W alloy as a precursor and transferring the Pt in the Pt-W alloy to Cu, an alloy material containing W and Cu, which was previously thought not to form an alloy, can be produced. Such an alloy material can be a novel joining material that realizes suitable joining between a tungsten member and a member made of a different metal.

[0010] The manufacturing method disclosed herein is based on the above findings, and is a method for manufacturing a ternary two-phase alloy material (W-Pt-Cu alloy) in which a W phase and a Pt-Cu phase are mixed. This manufacturing method is characterized in that platinum (Pt) of a Pt-W alloy containing platinum (Pt) and tungsten (W) is transferred to a Cu source containing copper (Cu). As described above, this manufacturing method can manufacture a W-Pt-Cu alloy. And, this W-Pt-Cu alloy can exhibit suitable bonding with a W member because the interface between the W phase and the Pt-Cu phase is stable, and can exhibit suitable bonding with dissimilar metal members (Cu members, Pt members, etc.) because it has a Pt-Cu phase. That is, according to the technology disclosed herein, suitable bonding between a W member and a dissimilar metal member can be realized.

[0011] In a preferred embodiment of the manufacturing method disclosed herein, the Pt-W alloy is an intermetallic compound. An example of such an intermetallic compound Pt-W alloy is Pt2W. By using such Pt2W as a precursor, a W-Pt-Cu alloy in which the W phase and the Pt-Cu phase are finely mixed can be produced.

[0012] In a preferred embodiment of the production method disclosed herein, the Pt-W alloy is brought into contact with a Cu source. According to the study by the present inventors, direct contact between the Pt-W alloy and the Cu source causes migration of platinum (Pt) from the Pt-W alloy to copper (Cu), producing a W-Pt-Cu alloy.

[0013] In a preferred embodiment of the production method disclosed herein, the contacted Pt-W alloy and Cu source are preferably heated, which promotes the migration of platinum (Pt) from the Pt-W alloy to copper (Cu), thereby efficiently producing the W-Pt-Cu alloy.

[0014] In a preferred embodiment of the manufacturing method disclosed herein, the method includes a Pt-W alloy production process in which a Pt source containing platinum (Pt) is contacted with a W source containing tungsten (W) and a heat treatment is performed to produce a Pt-W alloy, and a W-Pt-Cu alloy production process in which a Pt-W alloy is contacted with a Cu source and a heat treatment is performed to transfer platinum (Pt) in the Pt-W alloy to Cu to produce a W-Pt-Cu alloy. As described above, in order to generate a W-Pt-Cu alloy, it is necessary to use a Pt-W alloy as a precursor. Such a Pt-W alloy can be efficiently generated by performing a heat treatment while the Pt source and the W source are in contact with each other. In addition, according to the study by the present inventors, even if the Pt-W alloy and the Cu source are only brought into contact with each other, migration (diffusion) of Pt from the Pt-W alloy to Cu occurs, and the W-Pt-Cu alloy is generated. However, it takes a very long time to generate a sufficient W-Pt-Cu alloy only by contacting the Pt-W alloy with the Cu source. For this reason, in this embodiment, a heat treatment is performed while the Pt-W alloy and the Cu source are in contact with each other, and migration of Pt from the Pt-W alloy to Cu is promoted. As described above, according to the manufacturing method of this embodiment, the W-Pt-Cu alloy can be efficiently generated.

[0015] In the embodiment in which the Pt-W alloy forming step is carried out, the heating temperature in the Pt-W alloy forming step is preferably 800° C. or more and 1200° C. or less. The heating time in the Pt-W alloy forming step is preferably 0.5 hours or more and 3 hours or less. By setting the conditions (heating temperature, heating time) of the Pt-W alloy forming step in this way, the Pt-W alloy can be efficiently formed, thereby improving the productivity of the W-Pt-Cu alloy.

[0016] In the embodiment in which the W-Pt-Cu alloy forming step is carried out, the heating temperature in the W-Pt-Cu alloy forming step is preferably 800° C. or more and 1200° C. or less. The heating time in the W-Pt-Cu alloy forming step is preferably 0.5 hours or more and 3 hours or less. By setting the conditions of the W-Pt-Cu alloy forming step (heating temperature, heating time) in this way, it is possible to appropriately cause the migration of Pt from the Pt-W alloy to Cu, thereby improving the productivity of the W-Pt-Cu alloy.

[0017] In another preferred embodiment of the manufacturing method disclosed herein, a heat treatment is performed with a Pt source containing platinum (Pt) interposed between a W source containing tungsten (W) and a Cu source, thereby generating a Pt-W alloy at the boundary between the W source and the Pt source, and transferring the platinum (Pt) in the Pt-W alloy to Cu to generate a W-Pt-Cu alloy. In the above-mentioned embodiment, the W-Pt-Cu alloy is produced by performing two or more heat treatments including the Pt-W alloy production step and the W-Pt-Cu alloy production step. However, the production method disclosed herein is not limited to the above-mentioned embodiment. For example, it has been confirmed by experiments that the W-Pt-Cu alloy can be produced even when the W source and the Cu source are heated together with the Pt source interposed between them. Specifically, when the W source, the Pt source, and the Cu source are heated together as in this embodiment, the Pt-W alloy is produced at the boundary between the W source and the Pt source. Then, as the heat treatment proceeds further, the Pt of the Pt-W alloy moves to the Cu while the Pt-W alloy and the Cu (including the Pt-Cu alloy) are finely mixed. As a result, the W-Pt-Cu alloy in which the W phase and the Pt-Cu phase are mixed is produced between the W source and the Cu source.

[0018] In the embodiment in which the W source, the Pt source, and the Cu source are heated together, the temperature of the heat treatment is preferably 800° C. or more and 1200° C. or less. The time of the heat treatment is preferably 0.5 hours or more and 3 hours or less. By setting the heating conditions in this way, the generation of the Pt-W alloy and the migration of Pt from the Pt-W alloy to Cu can be appropriately caused, and the W-Pt-Cu alloy can be efficiently produced.

[0019] Furthermore, in an embodiment in which the W source, the Pt source, and the Cu source are heated together, in the heat treatment, 0.5 g / mm 2 More than 5g / mm 2 It is preferable to apply pressure at the following pressure. This allows each material to adhere closely to each other, further improving the production efficiency of the W-Pt-Cu alloy.

[0020] In another embodiment of the manufacturing method disclosed herein, an intermediate metal member is interposed between the Pt-W alloy and the Cu source. In each of the above-mentioned embodiments, the Pt-W alloy and the Cu source are in direct contact with each other, but the manufacturing method disclosed herein is not limited to such an embodiment. According to an experiment conducted by the present inventor, even when another metal member (intermediate metal member) is interposed between the Pt-W alloy and the Cu source, migration of platinum (Pt) from the Pt-W alloy to copper (Cu) occurs, and a W-Pt-Cu alloy is produced.

[0021] In addition, even in the above-mentioned embodiment in which the intermediate metal member is interposed, it is preferable to heat the contacted Pt-W alloy, intermediate metal member, and Cu source, which promotes the migration of Pt from the Pt-W alloy to Cu, thereby improving the production efficiency of the W-Pt-Cu alloy.

[0022] Furthermore, in the above-mentioned embodiment in which the intermediate metal member is interposed, it is preferable that the intermediate metal member contains at least Pt, which allows the migration of Pt from the Pt-W alloy to Cu to occur more suitably, thereby further improving the production efficiency of the W-Pt-Cu alloy.

[0023] Next, as another aspect of the technology disclosed herein, an alloy material is provided. The alloy material disclosed herein is characterized by the mixture of a W phase mainly composed of tungsten (W) and a Pt-Cu phase containing platinum (Pt) and copper (Cu). Such an alloy material exhibits suitable bonding properties to W members because the interface between the W phase and the Pt-Cu phase is stable. On the other hand, since the Pt-Cu phase is mixed in this alloy material, it exhibits suitable bonding properties to dissimilar metal members (Cu members, Pt members, etc.). Therefore, the alloy material disclosed herein can be used as a bonding material for bonding W members and dissimilar metal members. In addition, since this alloy material contains W, which is a high melting point metal, it is expected to exhibit superior heat resistance compared to conventional general brazing materials. Furthermore, since this alloy material is expected to have a thermal expansion coefficient close to that of the W member, it is also expected to suppress deterioration of the joint due to stress caused by the difference in the amount of expansion and contraction.

[0024] In addition, a preferred embodiment of the alloy material disclosed herein is characterized in that a plurality of W phases are present in a matrix made of Pt-Cu phase. In this way, by adopting a structure in which W phases and Pt-Cu phases are mixed throughout the structure of the alloy material, it is possible to exhibit more suitable bondability to both tungsten members and members of dissimilar metals.

[0025] In a preferred embodiment of the alloy material disclosed herein, a 0.001 μm area was observed by SEM. 2 ~1μm 2 (Preferably 0.001 μm 2 ~0.1μm 2 ) W phase is 0.2 places / μm 2 The alloy material has a W phase region having a density of at least a certain amount and a length of at least 10 μm in a predetermined direction. In this way, the alloy material having a W phase region having a density of at least a certain amount and a length of at least 10 μm in a predetermined direction can exhibit more suitable bondability to the W member.

[0026] In a preferred embodiment of the alloy material disclosed herein, the atomic number of tungsten atoms present in the W phase is 75 atm% or more when the total number of metal elements present in the W phase is 100 atm%, which makes it possible to obtain an alloy material that exhibits high bondability to tungsten members.

[0027] In addition, as another aspect of the technology disclosed herein, a bonded body is provided. The bonded body is characterized in that a first member containing tungsten and a second member are bonded via the W-Pt-Cu alloy material. As described above, the W-Pt-Cu alloy material can be suitably used as a bonding material for a metal member (W member) containing tungsten.

[0028] In a preferred embodiment of the bonded body disclosed herein, the first member includes at least one selected from the group consisting of tungsten, tungsten nitride, tungsten carbide, tungsten carbonitride, copper-tungsten composite material, and silver-tungsten composite material. The alloy material disclosed herein can exhibit suitable bondability to the first member made of the above-mentioned W-based material.

[0029] In a preferred embodiment of the joint disclosed herein, the second member is characterized by including at least one selected from the group consisting of copper, platinum, platinum-copper alloy, platinum-tungsten alloy, and copper alloy. The alloy material disclosed herein can exhibit particularly favorable bonding properties to dissimilar metal members including at least one of Cu, Pt, and W as described above. In addition, the second member of the joint disclosed herein is not limited to the dissimilar metal members as described above, and may be the same tungsten member as the first member. That is, the W-Pt-Cu alloy material disclosed herein can be used not only for bonding a tungsten member and a dissimilar metal member, but also for bonding tungsten members together. [Brief description of the drawings]

[0030] [Figure 1] FIG. 1 is a cross-sectional view illustrating an alloy material according to an embodiment. [Diagram 2] FIG. 1 is a cross-sectional view that illustrates a bonded body according to an embodiment. [Diagram 3] 1 is a cross-sectional SEM image of analysis sample A-1. [Figure 4] (a) is an elemental map of W based on EDX analysis of the analysis sample A-1, and (b) is an elemental map of Pt. [Diagram 5](a) is the EDX spectrum in the region α in FIG. 3(b), and (b) is the EDX spectrum in the region β. [Figure 6] 4 is a graph showing the concentration distribution of W and Pt on the line segment X in FIG. [Figure 7] 3(b), (a) is an image showing the results of electron beam diffraction in region α, and (b) is an image showing the results of electron beam diffraction in region β. [Figure 8] (a) and (b) are images obtained by analyzing the crystal structure of analysis sample A-1 using EBSD, and (c) is an image of (b) in which tungsten and Pt2W have been separated and colored. [Figure 9] (a) is the grain size distribution in the W plate of the analysis sample A-1, and (b) is the grain size distribution in the Pt-W alloy. [Figure 10] (a) and (b) are cross-sectional SEM images of analytical sample A-2. [Figure 11] (a) is an image of the crystal structure of the analysis sample A-2 analyzed using EBSD, (b) is an image of (a) colored separately for the W phase and the Pt-Cu phase, (c) is an image showing the crystal orientation of the Pt-Cu phase crystal grains in (b), and (d) is an image showing the crystal orientation of the W phase crystal grains in (b). [Figure 12] (a) is the particle size distribution in the Pt-Cu phase of the analysis sample A-2, and (b) is the particle size distribution in the W phase. [Figure 13] (a) is a cross-sectional SEM image (250x) of sample 1, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 14] (a) is a cross-sectional SEM image (1000x) of sample 1, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 15] (a) is a cross-sectional SEM image (10,000x) of sample 1, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 16](a) is a cross-sectional SEM image (50,000x) of sample 1, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 17] 1 is a SEM image showing an area where elemental analysis was performed on Sample 1. [Figure 18] 1 shows SEM images of Sample 1, where (a) is an image showing the boundary between the Cu member and the W member, and (b) and (c) are further enlarged images of the boundary portion. [Figure 19] FIG. 2 shows an HAADF-STEM image and element mapping image of Sample 1. [Figure 20] 20 is an EDX spectrum of the W-Pt-Cu alloy in FIG. 19. [Figure 21] 1 shows an EDX spectrum of the W phase in the HAADF-STEM image of sample 1. [Figure 22] 1 shows an EDX spectrum of the Pt—Cu phase in the HAADF-STEM image of Sample 1. [Diagram 23] (a) is a cross-sectional SEM image (5000x) of sample 2, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 24] (a) is a cross-sectional SEM image (50,000x) of sample 2, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Diagram 25] 23(b) is a graph showing the concentration distribution of W, Pt, and Cu on the line segment X1 in Fig. 23(b), where (a) shows the analysis result of Pt, (b) shows the analysis result of W, and (c) shows the analysis result of Cu. [Figure 26] (a) is a cross-sectional SEM image (5000x) of sample 3, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 27] (a) is a cross-sectional SEM image (50,000x) of sample 3, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 28](a) is a cross-sectional SEM image (200,000x) of sample 3, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 29] (a) is a cross-sectional SEM image (5000x) of sample 4, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Diagram 30] (a) is a cross-sectional SEM image (50,000x) of the Pt-Cu layer of sample 4, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Diagram 31] (a) is a cross-sectional SEM image (50,000x) of the Pt-W layer of sample 4, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Diagram 32] (a) is a cross-sectional SEM image (50,000x) of the W-Pt-Cu layer of sample 4, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Diagram 33] (a) is a cross-sectional SEM image (50,000x) of the tungsten member of Sample 4, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Diagram 34] 29(a) is a graph showing the concentration distribution of W, Pt, and Cu on the line segment X2 in Fig. 29(a), where (a) shows the analysis result of Pt, (b) shows the analysis result of W, and (c) shows the analysis result of Cu. [Diagram 35] (a) is a backscattered electron image (5000x) of sample 4, (b) is an enlarged view (20000x) of region α in (a), and (c) is an enlarged view (20000x) of region β in (a). [Diagram 36] (a) is a cross-sectional SEM image (20,000x) of region α of sample 4, and (b) to (d) are elemental maps of Cu, Pt, and W, respectively, based on EDX analysis. [Figure 37] (a) is a cross-sectional SEM image (20,000x) of region β of sample 4, and (b) to (d) are elemental maps of Cu, Pt, and W, respectively, based on EDX analysis. [Figure 38] FIG. 13 shows an HAADF-STEM image and element mapping image of Sample 4. [Figure 39] 39 is a graph showing the concentration distributions of Pt, Cu, and W on the line segment X3 in FIG. 38. [Diagram 40] FIG. 13 shows HAADF-STEM images and element mapping images of the interfaces between the W plate of Sample 4, the W phase of the W—Pt—Cu layer, and the Pt—Cu phase of the W—Pt—Cu layer. [Diagram 41] 41 is a graph showing the concentration distributions of Pt, Cu, and W on the line segment X4 in FIG. 40. [Diagram 42] 41 is a graph showing the concentration distribution of O and Fe on the line segment X4 in FIG. 40. [Diagram 43] (a) is an image showing the results of electron beam diffraction in region α in Figure 38(a), (b) is an image showing the results of electron beam diffraction in region β, (c) is an image showing the results of electron beam diffraction in region γ, and (d) is an image showing the results of electron beam diffraction in region δ. [Diagram 44] FIG. 13 shows the results of an HAADF-STEM image and element mapping image of the W plate of Sample 4. [Diagram 45] 13A and 13B are diagrams showing the results of an HAADF-STEM image and element mapping image of the Pt—W layer of Sample 4. [Figure 46] 13A and 13B are diagrams showing the results of an HAADF-STEM image and element mapping image of a Pt—Cu layer of Sample 4. [Figure 47] FIG. 45 is an EDX spectrum in the Pt-Cu region in FIG. [Figure 48] FIG. 41 shows an EDX spectrum in the Pt-Cu region in FIG. [Figure 49] FIG. 46 is an EDX spectrum in the Pt-Cu region in FIG. [Figure 50] FIG. 47 is an EDX spectrum in the Pt-Cu region in FIG. [Figure 51](a) is a cross-sectional SEM image (5000x) of sample 5, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 52] (a) is a cross-sectional SEM image (50,000x) of sample 5, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Diagram 53] (a) is a cross-sectional SEM image (5000x) of sample 6, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 54] (a) is a cross-sectional SEM image (50,000x) of sample 6, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 55] (a) is a cross-sectional SEM image (5000x) of sample 7, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 56] (a) is a cross-sectional SEM image (50,000x) of the Pt-W layer of sample 7, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 57] (a) is a cross-sectional SEM image (50,000x) of the W-Pt-Cu layer of sample 7, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 58] (a) is a cross-sectional SEM image (50,000x) of the W plate of sample 7, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 59] (a) is a cross-sectional SEM image (50,000x) of the interface between the W plate and the W-Pt-Cu layer of sample 7, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 60] (a) is a cross-sectional SEM image (5000x) of a Cu-uncoated portion of sample 8, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 61](a) is a cross-sectional SEM image (50,000x) of a Cu-uncoated portion of sample 8, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 62] (a) is a cross-sectional SEM image (5000x) of the Cu-coated area of ​​sample 8, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 63] (a) is a cross-sectional SEM image (50,000x) of the W-Pt-Cu layer formed on the Cu-coated portion of sample 8, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 64] (a) is a cross-sectional SEM image (50,000x) of the W-Pt-Cu layer formed on the Cu-coated portion of sample 8, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 65] (a) is a cross-sectional SEM image (50,000x) of the boundary between the W plate and the W-Pt-Cu layer formed in the Cu-coated area of ​​sample 8, and (b) to (d) are elemental maps of W, Cu, and Pt, respectively, based on EDX analysis. [Figure 66] (a) is a cross-sectional SEM image (250x) of sample 9, and (b) to (d) are elemental maps of O, Cu, and W, respectively, based on EDX analysis. [Figure 67] (a) is a cross-sectional SEM image (1000x) of sample 9, and (b) to (d) are elemental maps of O, Cu, and W, respectively, based on EDX analysis. [Figure 68] (a) is a cross-sectional SEM image (5000x) of sample 9, and (b) to (d) are elemental maps of O, Cu, and W, respectively, based on EDX analysis. [Figure 69] (a) is a cross-sectional SEM image (50,000x) of sample 9, and (b) to (d) are elemental maps of O, Cu, and W, respectively, based on EDX analysis. [Figure 70] (a) is a cross-sectional SEM image (5000x) of Sample 10, (c) is an elemental map of W based on EDX analysis, and (d) is an elemental map of Pt. [Figure 71] 1 is a cross-sectional SEM image (5000x) of Sample 11. [Figure 72] 1 is a cross-sectional SEM image (50,000x) of Sample 11. [Figure 73] (a) is a cross-sectional SEM image (5000x) of sample 12, and (b) to (e) are elemental maps of W, Cu, Pt, and Au based on EDX analysis, respectively. [Figure 74] (a) is a cross-sectional SEM image (50,000x) of sample 12, and (b) to (e) are elemental maps of W, Cu, Pt, and Au based on EDX analysis, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] An embodiment of the technology disclosed herein will be described below. Matters other than those specifically mentioned in this specification and necessary for implementing the technology disclosed herein can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The technology disclosed herein can be implemented based on the contents disclosed in this specification and the technical common sense in the relevant field. In this specification, "A to B (A and B are numerical values)" means "A or more and B or less."

[0032] 1.Alloy material Fig. 1 is a cross-sectional view showing a schematic diagram of the alloy material according to the present embodiment. As shown in Fig. 1, the alloy material (W-Pt-Cu alloy) 10 according to the present embodiment is a ternary two-phase alloy material in which a W phase 12 and a Pt-Cu phase 14 are mixed (see Fig. 1). Each phase contained in the alloy material 10 according to the present embodiment will be described below.

[0033] (1)W phase The W phase 12 is a phase mainly composed of tungsten. In this specification, "mainly composed of tungsten" means that elements other than tungsten are not intentionally included. Therefore, a phase containing inevitable impurities (metal elements other than W) derived from raw materials, manufacturing processes, etc. as secondary components is included in the concept of "W phase" in this specification. For example, when the total number of metal elements in one phase of a two-phase alloy is 100 atm%, if the number of W atoms in the one phase is 75 atm% or more, it can be said that "a W phase mainly composed of tungsten is formed". From the viewpoint of improving the bondability between the alloy material 10 according to this embodiment and the W member, the number of W atoms in the W phase is preferably 77.5 atm% or more, more preferably 80 atm% or more, and particularly preferably 82.5 atm% or more. The upper limit of the number of W atoms in the W phase is not particularly limited, and may be 99.5 atm% or less, 97.5 atm% or less, 95 atm% or less, 92.5 atm% or less, or 90 atm% or less. In this specification, the "atomic number" is a value based on elemental analysis obtained by performing energy dispersive X-ray spectroscopy (EDX) on a cross-sectional SEM image of the alloy material.

[0034] Examples of unavoidable impurities that may be contained in the W phase 12 include copper (Cu), platinum (Pt), molybdenum (Mo), iron (Fe), cobalt (Co), nickel (Ni), gold (Au), and thorium (Th). Tungsten in the W phase 12 may exist in the form of a simple metal, a compound (oxide, etc.), or an alloy with other metal elements.

[0035] (2) Pt-Cu phase The Pt-Cu phase 14 is a phase having platinum (Pt) and copper (Cu). The Pt-Cu phase 14 may contain Pt and Cu, and is not intended to exclude the inclusion of a third metal element other than Pt and Cu. Furthermore, the Pt-Cu phase 14 does not need to be mainly composed of Pt and Cu, and may be mainly composed of the above-mentioned third metal element. Although details will be described later, depending on the material and manufacturing method used in manufacturing the alloy material 10, the third metal element other than Pt and Cu can be the main component of the Pt-Cu phase 14. Specifically, when the total number of metal atoms in the Pt-Cu phase is 100 atm%, the total number of Pt atoms and Cu atoms may be 20 atm% or more, 30 atm% or more, or 40 atm% or more. In consideration of the bondability with copper members, the total number of Pt atoms and Cu atoms is preferably 50 atm% or more, more preferably 65 atm% or more, even more preferably 75 atm% or more, and particularly preferably 85 atm% or more. On the other hand, the upper limit of the total number of Pt atoms and Cu atoms in the Pt-Cu phase is not particularly limited, and may be 99.5 atm% or less, 99 atm% or less, 97.5 atm% or less, or 95 atm% or less. Examples of the third metal element that may be included in the Pt-Cu phase 14 include W, Mo, Fe, Pd, Ir, Au, Co, Ni, Zn, Al, Sn, Pb, Mn, Ag, and Th. Among these third metal elements, metal elements that are more likely to form an alloy with Cu than W (e.g., Au, Co, Ni, Zn, Al, Sn, Pb, Mn, Ag, Th, etc.) can be the main component of the Pt-Cu phase 14.

[0036] In addition, the number of Pt and Cu atoms present in the Pt-Cu phase is not particularly limited. For example, the number of Pt atoms present in the Pt-Cu phase may be 0.1 atm% or more, 0.5 atm% or more, or 1 atm% or more. On the other hand, the upper limit of the number of Pt atoms may be 25 atm% or less, 22.5 atm% or less, 20 atm% or less, or 17.5 atm% or less. In addition, the number of Cu atoms in the Pt-Cu phase may be 15 atm% or more, 20 atm% or more, 30 atm% or more, or 40 atm% or more. In consideration of the bondability with the copper member, the number of Cu atoms is preferably 50 atm% or more, more preferably 65 atm% or more, even more preferably 75 atm% or more, and particularly preferably 80 atm% or more. On the other hand, the upper limit of the number of Cu atoms may be 85 atm% or less, 82.5 atm% or less, or 80 atm% or less. As described above, the number of Pt and Cu atoms present in the Pt-Cu phase is not particularly limited. For example, by bringing the alloy material 10 into contact with a Cu member, Pt can be diffused into the Cu member, thereby reducing the number of Pt atoms in the alloy material 10. Similarly, by bringing the alloy material 10 into contact with a member (e.g., Au, Ni) that can diffuse Cu, the number of Cu atoms in the alloy material 10 can be reduced.

[0037] (3) Structure of alloy materials Next, the structure of the alloy material 10 according to this embodiment will be described. As shown in FIG. 1, the alloy material 10 according to this embodiment is a ternary two-phase alloy in which the above-mentioned W phase 12 and Pt-Cu phase 14 are mixed. That is, the alloy material 10 according to this embodiment exists in a state in which the W phase 12 and the Pt-Cu phase 14 are mixed in the entire metal structure. Typically, in this alloy material 10, a matrix made of the Pt-Cu phase 14 is formed, and a plurality of W phases 12 exist in the matrix of the Pt-Cu phase 14. Thus, in the alloy material 10 according to this embodiment, the interface between the W phase 12 and the Pt-Cu phase 14 is stable, so that the alloy material 10 can exhibit high bondability to the W member, while the alloy material 10 has the Pt-Cu phase 14, so that the alloy material 10 can exhibit suitable bondability to dissimilar metal members (Cu members, Pt members, etc.). An example of the alloy material (W-Pt-Cu alloy) disclosed herein is a form in which a plurality of long island-shaped W phases are scattered so as to extend in the thickness direction, and a Pt-Cu phase is formed so as to fill the spaces between the plurality of W phases (see, for example, FIG. 16(a), FIG. 19, etc.). However, the shape of the W phase is not limited to the above-mentioned long island shape, and may be substantially spherical (see, for example, FIG. 52(a)).

[0038] The alloy material disclosed herein is not limited to a form in which multiple W phases are scattered throughout the alloy material. For example, W phase may be present at a certain density or higher in a specific region of the Pt-Cu phase (see FIG. 73(a)). In this specification, the region in which W phase is present at a certain density or higher is referred to as a "W phase-existing region." More specifically, in this specification, a "W phase-existing region" refers to a region having an area of ​​0.001 μm2 or less when observed with an SEM. 2 ~1μm 2 (Preferably 0.001 μm 2 ~0.1μm 2 ) W phase is 1μm 2 In the Pt-Cu phase in the range of 0.2 points / μm 2It is a region where the W phase exists at a density of 10 μm or more. When such a W phase exists in a predetermined direction, it is possible to exhibit suitable bonding properties to both the W component and the dissimilar metal component. The above-mentioned "direction in which the W phase exists" is not particularly limited. In other words, as long as the W phase exists in a region where the W phase is densely packed to a certain degree or more and exists in at least one direction (for example, any one of the thickness direction, width direction, and depth direction) of 10 μm or more, it is possible to obtain an alloy material that exhibits suitable bonding properties to both the tungsten component and the dissimilar metal component. As described above, the density of the W phase in the W phase exists in the W phase exists in a region where the W phase exists at a density of 0.2 points / μm or more. 2 However, when considering the bondability with W components, the density of the W phase in the W phase-existing region should be 0.3 points / μm 2 More than 0.5 points / μm is more appropriate. 2 The above is more appropriate. From the viewpoint of further improving the bondability with the W member, the density of the W phase in the W phase-existing region is set to 0.5 points / μm 2 More than 1 location / μm is preferable. 2 More preferably, 1.5 points / μm or more 2 More preferably, 2 points / μm 2 On the other hand, when considering the bondability with dissimilar metal members (Cu members, etc.), the density of the W phase in the W phase-existing region is preferably 100 points / μm 2 The following is appropriate: 50 points / μm 2 Less than 10 points / μm is preferable. 2 Less than 7.5 points / μm is more preferable. 2 Less than 5 points / μm is more preferable. 2 Particularly preferred is less than 4 points / μm 2 It can be the following:

[0039] The average area of ​​each W phase is 1 μm 2 Less than 0.75 μm is preferable. 2 Less than 0.5 μm is more preferable. 2 Less than 0.25 μm is more preferable. 2The following is particularly preferred. The presence of such minute W phases in the Pt-Cu phase matrix allows more suitable bonding to both the tungsten member and the dissimilar metal member. The lower limit of the average area of ​​the W phase is not particularly limited and is 0.001 μm 2 It may be 0.005 μm or more. 2 It may be 0.01 μm or more. 2 It may be 0.05 μm or more. 2 The "average area of ​​the W phase" can be obtained by extracting 50 or more (preferably 85) W phases confirmed by SEM observation and calculating the average value of the areas of the extracted W phases.

[0040] In addition, it is preferable that the crystal grains constituting the W phase are fine. As an example, the D 50 The grain size is preferably 1000 nm or less, more preferably 900 nm or less, further preferably 800 nm or less, and particularly preferably 700 nm or less. 50 The lower limit of the particle size is not particularly limited, and may be 100 nm or more, 200 nm or more, 300 nm or more, or 400 nm or more. On the other hand, it is preferable that the crystal grains constituting the Pt-Cu phase are also fine. For example, the D of the crystal grains constituting the Pt-Cu phase 50 The particle size is preferably 800 nm or less, more preferably 600 nm or less, further preferably 400 nm or less, and particularly preferably 200 nm or less. 50The lower limit of the particle size is not particularly limited, and may be 20 nm or more, 40 nm or more, 60 nm or more, or 80 nm or more. Since the W phase and the Pt-Cu phase are each composed of such fine crystal grains, the W phase and the Pt-Cu phase can be suitably mixed, and the bondability between the W member and the dissimilar metal member can be further improved. When comparing the sizes of the crystal grains of the W phase and the Pt-Cu phase relatively, it is preferable that the W phase is composed of relatively large crystal grains and the Pt-Cu phase is composed of relatively small crystal grains. In this specification, the term "D of crystal grains" refers to the grain size of the W phase and the Pt-Cu phase. 50 "Particle size" refers to the cumulative 50% from the fine particle side in the grain size distribution of crystal grains based on the number of grains. Also, "crystal grain size" is the "circle equivalent diameter of crystal grains" obtained by performing crystal analysis using electron backscatter diffraction (EBSD) on SEM images of alloy materials.

[0041] 2.Zygote Next, a bonded body in which two kinds of members are bonded together using the above-mentioned alloy material 10 will be described. FIG. 2 is a cross-sectional view that shows a schematic diagram of a bonded body according to this embodiment. In this bonded body 100, a first member (W member) 20 containing tungsten and a second member 30 are bonded together via the above-mentioned alloy material 10. As described above, in the alloy material 10 according to this embodiment, the interface between the W phase and the Pt-Cu phase is stable, so that the alloy material 10 can exhibit suitable bonding properties to the W member 20. On the other hand, since the Pt-Cu phase 14 is present throughout the entire metal structure of the alloy material 10, the alloy material 10 can also be suitably bonded to dissimilar metal members that are suitably bonded to the Pt-Cu alloy. For this reason, the alloy material 10 disclosed herein functions as a bonding material that bonds the first member (W member) 20 and the second member 30.

[0042] Furthermore, since the alloy material 10 contains W, a high melting point metal, it can exhibit superior heat resistance compared to conventional brazing materials. Furthermore, since the alloy material 10 has a thermal expansion coefficient close to that of the W member 20, damage to the joint (alloy material 10) caused by the large stress due to the difference in the amount of expansion and contraction can be suppressed. Therefore, the joint 100 joined with the alloy material 10 is particularly expected to be used in ultra-high temperature parts such as divertors, accelerators, plasma discharge devices, high-temperature furnaces, and thin film forming devices.

[0043] The first member (W member) 20 is not particularly limited as long as it is a solid metal member containing W. Examples of materials for the W member 20 include tungsten, tungsten nitride, tungsten carbide, tungsten carbonitride, copper-tungsten alloy, and silver-tungsten alloy. The first member (i.e., W member) in this specification is not limited to a member made of only the above-mentioned tungsten material, and may be a composite material made of a tungsten material and another material. Here, examples of materials that can be combined with the tungsten material include various metal materials such as copper (Cu), platinum (Pt), molybdenum (Mo), iron (Fe), cobalt (Co), nickel (Ni), gold (Au), and thorium (Th), and high-melting point ceramics such as thoria (ThO2) and yttria. For convenience of explanation, a plate-shaped W member 20 is shown in FIG. 2, but the shape of the W member is not particularly limited. For example, the shape of the W member can be any shape commonly used for metal members, such as a cylinder or a column, without any particular limitations.

[0044] On the other hand, the second member 30 is not particularly limited as long as it is a member that can be suitably joined to the alloy material (W-Pt-Cu alloy) 10, and various members can be used without particular restriction. A suitable example of the second member 30 is a dissimilar metal member mainly composed of a metal element other than tungsten. An example of such a dissimilar metal member is a metal member containing Cu or Pt. Specific examples of such dissimilar metal members include a Cu member, a Pt member, and a Pt-Cu alloy member. In addition, the dissimilar metal member may be a metal member (Ni member, Co member, etc.) that has good bonding properties with Cu or Pt. The material of the second member 30 can be appropriately changed according to the main component of the Pt-Cu phase 14 of the alloy material 10, and is not limited to the above-mentioned metal member that has good bonding properties with Cu or Pt. For example, in the production of an alloy material described later, a third metal element other than Pt or Cu (e.g., Au, Ni, Zn, etc.) can be mixed into a Cu source to form a Pt-Cu phase 14 containing the third metal element. When such a Pt-Cu phase 14 containing a third metal element is formed, a metal member having good bonding compatibility with the third metal element can be used as the second member 30. As an example, when a Pt-Cu phase 14 containing Au is formed, in addition to the above-mentioned Cu member, Pt member, and Pt-Cu alloy member, Au members, Ag members, etc. can be used as bonding objects. In addition, the term "dissimilar metal members" in this specification refers to metal members whose main component is a metal element other than tungsten, and does not intend to exclude metal members containing W as a secondary component. In other words, the dissimilar metal members may be alloys containing tungsten.

[0045] Furthermore, the second member 30 is not limited to the dissimilar metal members as described above. For example, the alloy material 10 disclosed herein is not limited to the joining of a W member and a dissimilar metal member, and can also be used as a joining material for joining W members together. That is, the second member 30 may be a W member of the same type as the first member 20 described above (for example, tungsten, tungsten nitride, tungsten carbide, tungsten carbonitride, etc., and composite materials containing these). In general, W members are difficult to directly weld because of their high melting points. However, by using the alloy material disclosed herein, W members can be easily joined together. Furthermore, the second member 30 does not have to be a metal member. For example, the second member 30 may be a ceramic such as thoria (ThO2) or yttria, or a glass. The alloy material 10 disclosed herein can exhibit suitable joining properties even with such nonmetallic members.

[0046] 3. Manufacturing method of alloy materials Next, a method for producing the alloy material disclosed herein will be described. The alloy material disclosed herein can be produced by preparing a Pt-W alloy containing Pt and W and a Cu source containing copper (Cu) as precursors, and transferring Pt from the Pt-W alloy to the Cu source. As an example, the transfer of Pt from the Pt-W alloy to the Cu source occurs by contacting the Pt-W alloy with the Cu source. Specifically, when the Pt-W alloy and the Cu source are contacted, Pt diffuses (transfers) from the Pt-W alloy to the Cu source. At this time, since the diffusion of Pt is likely to occur at the grain boundaries between the crystal grains of the Pt-W alloy and Cu, the diffusion of Pt proceeds while the crystal grains of the Pt-W alloy and Cu are finely intermingled. As a result, a ternary two-phase alloy material (W-Pt-Cu alloy) is produced that is a mixture of a Pt-Cu phase containing Pt and Cu, and a W phase resulting from Pt removal from a Pt-W alloy.

[0047] Here, to produce a W-Pt-Cu alloy, it is sufficient to be able to move Pt in a Pt-W alloy to Cu, and the specific procedure is not particularly limited. That is, the method for producing an alloy material disclosed herein includes a plurality of production methods with different specific procedures (steps). Hereinafter, an example (first embodiment) of the production method disclosed herein will be described.

[0048] (1) First embodiment The manufacturing method according to this embodiment includes a Pt-W alloy forming step and a W-Pt-Cu alloy forming step. Each step will be described below.

[0049] (a) Pt-W alloy production process In this process, a heat treatment is performed while a Pt source containing platinum (Pt) and a W source containing tungsten (W) are in contact with each other. This makes it possible to easily generate a Pt-W alloy, which is a precursor of a W-Pt-Cu alloy. The Pt-W alloy generated in this process is not particularly limited as long as it contains Pt and W. An example of such a Pt-W alloy is an intermetallic compound (e.g., Pt2W) containing Pt and W in a predetermined integer ratio. This type of intermetallic compound has very fine crystal grains, so by using it as a precursor of a W-Pt-Cu alloy, an alloy material in which the W phase and the Pt-Cu phase are finely mixed can be generated. Specifically, the D of the crystal grains of the Pt-W alloy can be obtained by using the intermetallic compound as a precursor of the W-Pt-Cu alloy. 50 The particle size is suitably 2000 nm or less, preferably 1500 nm or less, more preferably 1000 nm or less, further preferably 500 nm or less, and particularly preferably 200 nm or less. 50 The lower limit of the particle size is not particularly limited, and may be 40 nm or more, 60 nm or more, 80 nm or more, or 100 nm or more.

[0050] The W source used in this step may be any material containing W element, and the detailed components and form are not particularly limited. Examples of such W sources include powder materials containing tungsten particles, solid or solution compounds containing tungsten, and solid metal members containing tungsten. The same type of material as the first member (W member) 20 described above may be used as the material of such W sources, and therefore a duplicated description will be omitted. In addition, as will be described in detail later, according to the manufacturing method disclosed herein, it is possible to manufacture only the alloy material 10 (see FIG. 1) alone, or to manufacture the alloy material 10 attached to the W member 20 (see FIG. 2). Although it is not intended to limit the manufacturing method disclosed herein, when manufacturing only the alloy material 10 alone, it is preferable to use a tungsten thin film having a thickness of 50 μm or less as the W source. As a result, the entire W source is used to form the alloy material 10, and therefore it is possible to form a single alloy material 10 to which no tungsten member is attached. Such a tungsten thin film can be formed, for example, by chemical vapor deposition or physical vapor deposition. From the viewpoint of more reliably forming the single alloy material 10, the thickness of the tungsten thin film is more preferably 20 μm or less, even more preferably 10 μm or less, and particularly preferably 5 μm or less. Also, from the viewpoint of preventing poor formation of the Pt-W alloy due to a shortage of W, the lower limit of the thickness of the tungsten thin film is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.5 μm or more, and particularly preferably 1 μm or more.

[0051] On the other hand, the Pt source may be a material containing Pt element, and the detailed components and form are not particularly limited. An example of such a Pt source is a Pt paste in which Pt powder is dispersed in a specific solvent. A Pt-W alloy can be easily produced by applying such a Pt paste to the surface of a W source and then performing a heat treatment. Such a Pt paste is not particularly limited except that it contains Pt particles, and a conventionally known Pt paste can be used as long as it does not impair the effects of the technology disclosed herein. As an example, the average particle size of the Pt particles in the paste is preferably 0.01 μm to 10 μm, more preferably 0.05 μm to 5 μm, and particularly preferably 0.1 μm to 1.0 μm, for example, 0.5 μm. In this specification, the "average particle size" is the average particle size of a plurality of particles (for example, 100 particles) measured based on SEM observation. In addition, the content (volume ratio) of Pt particles when the total volume of the Pt paste is 100 vol%, is preferably 1 vol% or more, more preferably 2.5 vol% or more, even more preferably 5 vol% or more, and particularly preferably 7.5 vol% or more. This can prevent poor formation of the Pt-W alloy due to a shortage of Pt. On the other hand, from the viewpoint of suppressing the viscosity increase of the Pt paste and improving workability, the upper limit of the content (volume ratio) of Pt particles is preferably 20 vol% or less, more preferably 17.5 vol% or less, even more preferably 15 vol% or less, and particularly preferably 12.5 vol% or less. In addition, the content (weight ratio) of Pt particles when the total weight of the Pt paste is 100 wt% is preferably 50 wt% or more, more preferably 55 wt% or more, even more preferably 60 wt% or more, and particularly preferably 65 wt% or more. On the other hand, the upper limit of the Pt particle content (weight ratio) is preferably 90 wt% or less, more preferably 85 wt% or less, even more preferably 80 wt% or less, and particularly preferably 75 wt% or less. Note that, as the components of the Pt paste other than the Pt particles (solvent, binder, dispersant, etc.), conventionally known components can be used without particular restrictions as long as they do not impede the effects of the technology disclosed herein, and detailed explanations are omitted because they do not characterize the technology disclosed herein.

[0052] In addition, from the viewpoint of preventing poor formation of the Pt-W alloy due to a shortage of Pt, the coating thickness of the Pt paste in this process is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more. On the other hand, the upper limit of the coating thickness of the Pt paste is preferably 100 μm or less, more preferably 80 μm or less, even more preferably 70 μm or less, and particularly preferably 60 μm or less. This prevents unreacted Pt from being generated on the surface of the Pt-W alloy, which would hinder the reaction between the Pt-W alloy and the Cu source in the W-Pt-Cu alloy generation process described below. The coating thickness of the Pt paste can be easily controlled to a desired thickness by adjusting the thickness of the metal mask used when applying the paste.

[0053] In addition, the heating temperature in this process is preferably 750°C or more, more preferably 800°C or more, even more preferably 850°C or more, and particularly preferably 900°C or more. This can improve the production efficiency of the Pt-W alloy. On the other hand, the upper limit of the heating temperature in this process is preferably 1250°C or less, more preferably 1200°C or less, even more preferably 1150°C or less, and particularly preferably 1100°C or less. In addition, the heating time in this process is preferably 0.5 hours or more, more preferably 1 hour or more. This can appropriately form the Pt-W alloy. On the other hand, from the viewpoint of production efficiency, the upper limit of the heating time in this process is preferably 5 hours or less, more preferably 4 hours or less, and particularly preferably 3 hours or less. In this specification, the "heating temperature" refers to the maximum temperature in the heat treatment, and the "heating time" refers to the time for maintaining the maximum temperature. In addition, the atmosphere during the heat treatment is preferably set to a non-oxidizing atmosphere (neutral atmosphere, reducing atmosphere). Examples of reducing gases include hydrogen (H2) gas and hydrocarbon (CH4, C3H8, etc.) gas. Examples of neutral gases include nitrogen (N2) gas. Mixtures of these reducing gases and neutral gases can also be used. For example, a mixed gas in which hydrogen (H2) gas is mixed with nitrogen (N2) gas at a concentration of 1% to 5% (e.g., 3%) can be used.

[0054] From the viewpoint of preventing damage (cracks, etc.) due to a sudden change in volume during the heat treatment, it is preferable to carry out a drying treatment to dry the Pt paste before the heat treatment for forming the Pt-W alloy. The heating temperature in the drying treatment is preferably 60°C or higher, more preferably 80°C or higher, and particularly preferably 100°C or higher. On the other hand, from the viewpoint of preventing the above-mentioned cracks, the upper limit of the heating temperature in the drying treatment is preferably 140°C or lower, more preferably 130°C or lower. Also, the drying time is preferably 10 minutes or more and 60 minutes or less (for example, about 30 minutes).

[0055] In addition, when an organic component such as a binder is added to the Pt paste, a preliminary heating process (binder removal process) for removing the organic component may be performed before the heat treatment for generating the Pt-W alloy. If the W source is oxidized by this binder removal process to generate tungsten oxide, the generation of the Pt-W alloy may be inhibited. For this reason, the organic component (binder, etc.) added to the Pt paste is preferably a resin material (e.g., acrylic resin, etc.) that can be sufficiently thermally decomposed in a non-oxidizing atmosphere. From the viewpoint of reliably removing the organic component, the heating temperature in the binder removal process is preferably 145°C or higher, more preferably 150°C or higher, even more preferably 155°C or higher, and particularly preferably 160°C or higher. On the other hand, in order to prevent the generation of the Pt-W alloy from progressing during the binder removal process, the upper limit of the heating temperature in the binder removal process is preferably 500°C or lower, more preferably 450°C or lower, even more preferably 400°C or lower, and particularly preferably 350°C or lower. The heating time in the binder removal process is preferably 0.5 hours or more, and more preferably 1 hour or more. This allows organic components to be reliably removed. From the viewpoint of production efficiency, the upper limit of the heating time in the binder removal process is preferably 5 hours or less, more preferably 4 hours or less, even more preferably 3 hours or less, and particularly preferably 2 hours or less.

[0056] (b) W-Pt-Cu alloy formation process In this process, a heat treatment is performed while the Cu source, which is a material containing Cu as a main component, is in contact with the Pt-W alloy. This causes the movement (typically diffusion) of Pt from the Pt-W alloy to Cu to proceed rapidly. At this time, the crystal grains of the Pt-W alloy and Cu are finely mixed together, and the diffusion of Pt proceeds. Meanwhile, W in the Pt-W alloy is hardly dissolved in Cu. Therefore, Pt is removed from the Pt-W alloy to Cu, and a W phase containing W as a main component is formed. Meanwhile, by supplying Pt to Cu, a Pt-Cu phase is formed so as to be filled around the W phase. In this way, according to the manufacturing method of this embodiment, a ternary two-phase alloy material (W-Pt-Cu alloy) in which W and Cu, which do not normally form an alloy, are mixed can be manufactured.

[0057] As described above, when the Cu source is brought into contact with the Pt-W alloy, the migration (diffusion) of Pt from the Pt-W alloy to Cu occurs, so that the W-Pt-Cu alloy can be produced without performing a heat treatment or the like. However, when the W-Pt-Cu alloy production process accompanied by a heat treatment is carried out as in this embodiment, the diffusion of Pt into Cu proceeds rapidly, so that the production efficiency of the W-Pt-Cu alloy can be significantly improved. The maximum temperature in the heat treatment is preferably 750°C or higher, more preferably 800°C or higher, even more preferably 850°C or higher, and particularly preferably 900°C or higher. This more suitably promotes the diffusion of Pt, and the W-Pt-Cu alloy can be efficiently formed. On the other hand, the upper limit of the maximum firing temperature is preferably 1500°C or lower, more preferably 1400°C or lower, even more preferably 1300°C or lower, and particularly preferably 1200°C or lower. The firing time in this process is preferably 1 hour or more, and more preferably 1.5 hours or more. This makes it possible to form a W-Pt-Cu alloy in which the W phase and the Pt-Cu phase are sufficiently mixed. From the viewpoint of production efficiency, the upper limit of the firing time in this step is preferably 3 hours or less, and more preferably 2.5 hours or less.

[0058] In addition, the firing atmosphere in this step is preferably set to a non-oxidizing atmosphere (for example, a neutral atmosphere, an inert atmosphere, or a reducing atmosphere). Examples of reducing gases include hydrogen (H2) gas and hydrocarbon (CH4, C3H8, etc.) gas. Examples of inert gases include argon (Ar) gas, and examples of neutral gases include nitrogen (N2) gas and ammonia. A mixture of reducing gas and inert gas (or neutral gas) can also be used. For example, a mixed gas in which hydrogen gas is mixed with nitrogen gas at a concentration of 1% to 5% (for example, 3%) can be used.

[0059] In this process, the Pt-W alloy and the Cu source were sandwiched between two 0.5 g / mm 2 or more (more preferably 1g / mm 2 More preferably, 1.5 g / mm 2 It is preferable to carry out the firing process while applying a load of 10 g / mm or more. This prevents the formation of a gap between the Cu source and the Pt-W alloy, and allows the W-Pt-Cu alloy to be formed more efficiently. There is no particular upper limit to the load applied to the Pt-W alloy and the Cu source, and it is generally 10 g / mm or more. 2 It may be less than 8g / mm 2 It may be less than 6g / mm 2 It may be less than 5g / mm 2 It may be the following.

[0060] The Cu source used in this process may be a material containing Cu, and the components thereof are not particularly limited. Specifically, the Cu source is not limited to Cu, and may contain a metal element other than Cu. In this case, by mixing a third metal element other than Pt or Cu into the Cu source, the Pt-Cu phase of the manufactured W-Pt-Cu alloy can contain the third metal element. This can improve the bondability to dissimilar metal members mainly composed of a metal element other than Cu or Pt. Here, examples of the third metal element that can be mixed into the Cu source include gold (Au), nickel (Ni), aluminum (Al), tin (Sn), zinc (Zn), silica (Si), iron (Fe), manganese (Mn), cobalt (Co), and beryllium (Be).

[0061] On the other hand, the shape of the Cu source is not particularly limited, and may be a solid metal member (Cu member) containing Cu, or may be a Cu paste in which Cu powder is dispersed in a solvent. As an example, when only an alloy material is produced alone, it is preferable to use a copper paste applied to a certain thickness or less as the Cu source. As a result, all of the Cu source is used to form the alloy material, so that a single alloy material to which no copper member is attached can be formed. In addition, instead of the copper paste, for example, a copper thin film attached by chemical vapor deposition or the like may be formed. Note that, from the viewpoint of reliably forming a single alloy material, the thickness of the Cu source is preferably 100 μm or less, more preferably 80 μm or less, even more preferably 70 μm or less, and particularly preferably 60 μm or less. On the other hand, from the viewpoint of preventing poor formation of the W-Pt-Cu alloy due to a shortage of Cu, the lower limit of the thickness of the Cu source is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more.

[0062] In addition, when Cu paste is used as the Cu source, the average particle size of Cu particles in the paste is preferably 0.01 μm to 10 μm, more preferably 0.1 μm to 5 μm, and particularly preferably 0.5 μm to 2 μm, for example, 1 μm. In addition, when the total volume of the Cu paste is 100 vol%, the content (volume ratio) of Cu particles is preferably 5 vol% or more, more preferably 10 vol% or more, even more preferably 15 vol% or more, and particularly preferably 20 vol% or more. This can prevent poor formation of Pt-W alloy due to Cu shortage. On the other hand, from the viewpoint of suppressing the viscosity increase of the copper paste and improving the workability, the upper limit of the content (volume ratio) of Cu particles is preferably 55 vol% or less, more preferably 50 vol% or less, even more preferably 45 vol% or less, and particularly preferably 40 vol% or less. In addition, when the total weight of the Cu paste is 100wt%, the content (weight ratio) of the Cu particles is preferably 60wt% or more, more preferably 65wt% or more, even more preferably 70wt% or more, and particularly preferably 75wt% or more. On the other hand, the upper limit of the content (weight ratio) of the Cu particles is preferably 95wt% or less, more preferably 90wt% or less, and particularly preferably 85wt% or less. In addition, the components of the Cu paste other than the Cu particles (solvent, binder, dispersant, etc.) can be any conventionally known components without any particular restrictions as long as they do not impede the effects of the technology disclosed herein, and detailed explanations are omitted because they do not characterize the technology disclosed herein. In addition, as described above, when a third metal element is added to the Cu source, it is preferable to add a powder of the third metal element to the Cu paste. This makes it easy to add the third metal element to the Cu source.

[0063] (2) Second embodiment Next, another example (second embodiment) of the method for producing an alloy material disclosed herein will be described.

[0064] In the first embodiment described above, the W-Pt-Cu alloy is produced by performing two or more heat treatments including the Pt-W alloy production step and the W-Pt-Cu alloy production step. However, the production method disclosed herein is not limited to the above embodiment. For example, it has been confirmed by experiments that the W-Pt-Cu alloy can be produced even when the W source and the Cu source are heated together with the Pt source interposed between them. Specifically, when the W source, the Pt source, and the Cu source are heated together as in this embodiment, the Pt-W alloy is produced at the boundary between the W source and the Pt source. Then, as the heat treatment proceeds further, the Pt of the Pt-W alloy moves to the Cu while the Pt-W alloy and the Cu (including the Pt-Cu alloy) are finely mixed. As a result, the W-Pt-Cu alloy in which the W phase and the Pt-Cu phase are mixed is produced between the W source and the Cu source. From the viewpoint of producing the W-Pt-Cu alloy reliably, it is preferable to perform the Pt-W alloy production step in advance to reliably produce the precursor (Pt-W alloy) and then produce the W-Pt-Cu alloy, as in the above-mentioned first embodiment. On the other hand, in consideration of production efficiency and production costs, it is preferable to produce the Pt-W alloy and the W-Pt-Cu alloy simultaneously, as in this embodiment.

[0065] In addition, the temperature of the heat treatment in this embodiment is preferably 750°C or more, more preferably 800°C or more, even more preferably 850°C or more, and particularly preferably 900°C or more. This more preferably promotes the diffusion of Pt, and allows the W-Pt-Cu alloy to be efficiently formed. On the other hand, the upper limit of the maximum firing temperature is preferably 1500°C or less, more preferably 1400°C or less, even more preferably 1300°C or less, and particularly preferably 1200°C or less. In addition, the firing time in this step is preferably 1 hour or more, more preferably 1.5 hours or more. This allows the W-Pt-Cu alloy to be formed in which the W phase and the Pt-Cu phase are sufficiently mixed. On the other hand, from the viewpoint of manufacturing efficiency, the upper limit of the firing time in this step is preferably 3 hours or less, more preferably 2.5 hours or less.

[0066] In the present embodiment, in the above-mentioned heat treatment, a 0.5 g / mm2 or more (more preferably 1g / mm 2 More preferably, 1.5 g / mm 2 It is preferable to carry out the firing process while applying a load of 10 g / mm or more. This prevents gaps from being generated between the Cu source, Pt source, and W source, and allows the W-Pt-Cu alloy to be formed more efficiently. There is no particular upper limit to the load when sandwiching the respective members, and it is preferably 10 g / mm 2 It may be less than 8g / mm 2 It may be less than 6g / mm 2 It may be less than 5g / mm 2 It may be the following.

[0067] 4. Other embodiments An embodiment of the technology disclosed herein has been described above. However, the above embodiment is not intended to limit the technology disclosed herein, and various modifications may be made.

[0068] For example, the various conditions described in each of the above-mentioned embodiments are examples of conditions for producing only the alloy material alone, and are not intended to limit the technology disclosed herein. Various conditions such as the W source, Cu source, Pt source, sintering temperature, and sintering time can be appropriately adjusted according to the shape and state of the target alloy material. As a specific example, in the above-mentioned embodiment, in order to produce only the alloy material alone, W paste or W thin film is used as the W source, and Cu paste or Cu thin film is used as the Cu source. However, by using a tungsten member having a predetermined thickness as the W source, an alloy material in a state of being joined with the tungsten member can be produced. According to this embodiment, the production of the alloy material and the joining process of the alloy material and the tungsten member can be performed simultaneously, which is preferable from the viewpoint of work efficiency, etc. Note that if the thickness of the tungsten member is 0.1 mm or more (preferably 0.2 mm or more, more preferably 0.3 mm or more), the tungsten member remains even after the W-Pt-Cu alloy is formed, so that an alloy material in a state of being joined with the tungsten member can be obtained.

[0069] Similarly, when the dissimilar metal members to be joined are Cu members, a copper member having a predetermined thickness can be used as the Cu source to produce an alloy material joined to the Cu member (dissimilar metal member), which is preferable from the viewpoint of work efficiency, etc. If the thickness of the copper member is 0.1 mm or more (preferably 0.2 mm or more, more preferably 0.3 mm or more), the copper member remains even after the W-Pt-Cu alloy is formed, and an alloy material joined to the copper member can be obtained.

[0070] In addition, by using a tungsten member having a predetermined thickness as a W source and a copper member having a predetermined thickness as a Cu source, a bonded body in which a W member and a Cu member are bonded via a W-Pt-Cu alloy can be manufactured. According to this manufacturing method, a desired bonded body can be efficiently manufactured. In addition, in the bonded body manufactured in this manner, all of the alloy material formed between the W member and the Cu member does not have to be composed of a W-Pt-Cu alloy. For example, a Pt-W alloy may be formed in the region of the alloy material on the W member side, or a Pt-Cu alloy may be formed in the region of the alloy material on the Cu member side.

[0071] Furthermore, in each of the above-mentioned embodiments, the Pt-W alloy and the Cu source are directly contacted. However, the manufacturing method disclosed herein is not limited to these embodiments, and the Pt-W alloy and the Cu source may be contacted through the intermediation of another metal member (intermediate metal member). The inventor has confirmed through experiments that even in such a case, migration of Pt from the Pt-W alloy to Cu occurs, and a W-Pt-Cu alloy is generated. An example of such an intermediate metal member is a metal member containing Pt. The intermediate metal member is preferably a metal member that diffuses the Cu component. For example, other than Pt, metals and alloys that can be alloyed (particularly solid-soluble) with Cu can be used. Specific examples of the intermediate metal member include metal members containing Ni, Au, Sn, Zn, etc., and copper alloys. Among these, Ni, Au, and Pt that can form a complete solid solution with Cu are particularly suitable as the intermediate metal member. Also, as in each of the above-mentioned embodiments, it is preferable to perform heat treatment even when an intermediate metal member is interposed. This can promote the migration of Pt from the Pt-W alloy to Cu. Note that the conditions for the heat treatment can be set to the same extent as in the above-mentioned embodiment, and therefore a duplicated description will be omitted.

[0072] In the above embodiment, the alloy material disclosed herein is used as a bonding material between a tungsten member and a dissimilar metal member. However, the alloy material disclosed herein is not limited to bonding materials, and is expected to be applied to various fields. Other examples of the use of the alloy material disclosed herein include a barrier film for protecting the surface of a metal member (e.g., a W member), a catalyst, etc. In addition, between the W phase and the Pt-Cu phase constituting the alloy material disclosed herein, the Pt-Cu phase is more easily dissolved in acid. For this reason, an alloy material in which a very fine W phase exists in a matrix of the Pt-Cu phase is produced, and the Pt-Cu phase of this alloy material is dissolved in acid, thereby producing very fine tungsten particles. That is, the alloy material disclosed herein can also be used to produce tungsten particles.

[0073] [Test example] Test examples relating to the present invention will be described below, but these test examples are not intended to limit the present invention.

[0074] A. First test In this test, the W-Pt-Cu alloy was produced by carrying out the Pt-W alloy production process and the W-Pt-Cu alloy production process as in the first embodiment described above. Various analyses were then carried out in each process to investigate the production mechanism of the W-Pt-Cu alloy.

[0075] 1.Pt-W alloy production process First, Pt paste was prepared by mixing Pt powder with an average particle size of 0.5 μm, a binder (acrylic resin), and a solvent (IBA: isobutyl alcohol). The content of Pt powder in the total weight of this Pt paste was set to 70 wt% (10 vol% by volume). Next, the Pt paste was applied to the surface of a tungsten plate (W plate) using a metal mask (thickness 50 μm × 20 mm × 20 mm). Next, a drying process (drying temperature: 120 ° C, drying time: 30 minutes) was performed to dry the Pt paste on the W plate surface. Then, the W plate to which the dried Pt paste was attached was subjected to a heat treatment to obtain an analysis sample A-1. The atmosphere in the heat treatment was set to a reducing atmosphere (N2-H2 (3%) gas). In this process, the heat treatment was carried out under the following conditions: the temperature was increased to 400°C at a rate of 4°C / min and held at that temperature for 1 hour, and then the temperature was increased to 1000°C at a rate of 4°C / min and held at that temperature for 2 hours.

[0076] The heat-treated analytical sample A-1 was sliced ​​using a focused ion beam scanning electron microscope (FIB-SEM) and a cross-sectional SEM image of the cut surface was taken (see FIG. 3). In this test, EDX analysis was performed on the cross-sectional SEM image (FIG. 3(b)) and elemental mapping images of W and Pt were obtained (see FIG. 4). In FIG. 4, (a) is the elemental map of W and (b) is the elemental map of Pt. From the results of these analyses, it was found that the heat-treated analytical sample A-1 included a W plate and a Pt-W alloy formed on the surface of the W plate.

[0077] Furthermore, in this test, EDX spectra were obtained for each of the regions α (W plate portion) and β (Pt-W alloy portion) in Figure 3(b). The EDX spectrum for region α is shown in Figure 5(a), and the EDX spectrum for region β is shown in Figure 5(b). Based on these EDX spectra, the abundance ratio of elements in each region was analyzed. As a result, in region α (W plate portion), the results were confirmed as Pt: 0 atm%, W: 99.05 atm%, and Fe: 0.95 atm%. On the other hand, in region β (Pt-W alloy portion), the results were confirmed as Pt: 64.52 atm%, W: 34.30 atm%, and Fe: 1.18 atm%. Furthermore, in this test, EDX line analysis was performed on the line segment X with a length of 7000 nm drawn in Figure 3(b) to examine the changes in the elemental concentrations (atm%) of W and Pt. The results are shown in Figure 6. As shown in FIG. 6, the W element, which was about 100 atm% in region α (W plate portion), decreased to about 33 atm% in region β (Pt-W alloy portion). On the other hand, in region β, the Pt element increased to 66 atm%. In this test, electron beam diffraction was performed in each region of region α (W plate portion) and region β (Pt-W alloy portion) in FIG. 3(b). The results are shown in FIG. 7. In FIG. 7, (a) is an image showing the result of electron beam diffraction in region α (W plate portion), and (b) is an image showing the result of electron beam diffraction in region β (Pt-W alloy portion). In this electron beam diffraction, a diffraction pattern of W was obtained in region α, and a diffraction pattern of at least the 011 plane of Pt2W was obtained in region β. From the analysis results, it was found that the Pt-W alloy generated in this process was an intermetallic compound (Pt2W) in which Pt and W were mixed in an integer ratio of 2:1.

[0078] Next, the crystal structure was analyzed using EBSD for the SEM image of the analysis sample A-1. The SEM / EBSD image of the analysis result is shown in Figure 8. Also, (c) in Figure 8 is a colored version of the SEM / EBSD image of Figure 8(b) with tungsten and Pt2W. Furthermore, based on the EBSD analysis result, the grain size of the crystal grains in each region of the W plate and the Pt-W alloy was measured. Specifically, the circle equivalent diameter of the crystal grains in the image in each region of the W plate and the Pt-W alloy was measured, and a grain size distribution based on the number was created. The results are shown in Figure 9. Note that (a) in Figure 9 is the grain size distribution of the crystal grains in the W plate, and (b) is the grain size distribution of the crystal grains in the Pt-W alloy. From these analysis results, it was found that the Pt-W alloy (Pt2W) formed on the W plate is composed of very fine crystal grains of several hundred nm.

[0079] 2.W-Pt-Cu alloy production process In this process, Cu powder with an average particle size of 1 μm, a binder (acrylic resin), and a solvent (IBA: isobutyl alcohol) were mixed to prepare a Cu paste. The content of Cu powder in the total weight of this Cu paste was set to 80 wt% (30 vol% by volume). Then, the Cu paste was applied to the surface of the Pt-W alloy side of the above-mentioned analysis sample A-1 using a metal mask (thickness 50 μm × 20 mm × 20 mm). Next, a drying process (drying temperature: 120 ° C, drying time: 30 minutes) was performed to dry the Cu paste on the surface of the analysis sample A-1, and then a heat treatment was performed to prepare the analysis sample A-2. The atmosphere for the heat treatment was set to a reducing atmosphere (N2-H2 (3%) gas). In this process, the heat treatment was carried out under the following conditions: the temperature was increased to 400°C at a rate of 4°C / min and held at that temperature for 1 hour, and then the temperature was increased to 1000°C at a rate of 4°C / min and held at that temperature for 2 hours.

[0080] In the analysis of this step, first, the analysis sample A-2 after the heat treatment was sliced ​​using FIB-SEM. Then, a cross-sectional SEM image of the cut surface was taken. The result is shown in FIG. 10. Next, the crystal structure of the analysis sample A-2 was analyzed using EBSD. The result is shown in FIG. 11. As shown in FIG. 11(b), it was found that a W-Pt-Cu alloy in which the W phase and the Pt-Cu phase were mixed was formed in the analysis sample A-2. It was also found that both the W phase and the Pt-Cu phase were composed of minute crystal grains. It was also found that the Pt-Cu phase had a random crystal orientation and was composed of particularly minute crystal grains, as shown in FIG. 11(c). On the other hand, it was found that the W phase was composed of crystal grains larger than the Pt-Cu phase, and the crystal orientation of the crystal grains was oriented in the

[0101] direction, as shown in FIG. 11(d).

[0081] Furthermore, in this test, the grain size of the crystal grains in the W-Pt-Cu alloy was measured based on the above-mentioned EBSD analysis results. Here, the circle equivalent diameter of the crystal grains constituting each phase of the W phase and the Pt-Cu phase was measured within the observation field of view, and the grain size distribution in each phase was obtained. The results are shown in Figure 12. Figure 12(a) shows the grain size distribution of the Pt-Cu phase, and (b) shows the grain size distribution of the W phase. As shown in Figure 12, the D of the W phase 50 The particle size is 621 nm, and the D of the Pt-Cu phase 50 The particle diameter was 102 nm, and it was found that both the W phase and the Pt-Cu phase were composed of very fine crystal grains. From the particle size distribution shown in FIG. 12 and the SEM / EBSD image shown in FIG. 11, it is inferred that the W-Pt-Cu alloy formed in the analysis sample A-2 has a morphology in which very small Pt-Cu phase crystal grains are filled between relatively large W phase crystal grains. In other words, from this analysis, it is understood that the W-Pt-Cu alloy is generated by the migration (diffusion) of Pt in the Pt2W alloy to Cu while the Pt2W alloy and Cu are mixed together.

[0082] B. Second Test In this test, as in the second embodiment described above, the W source and the Cu source were subjected to heat treatment together with the Pt source interposed between them. Various analyses were then performed on the obtained alloy material.

[0083] 1. Sample Preparation First, a plate-shaped tungsten member (thickness 0.3 mm, length 7.5 mm, width 7.5 mm) was prepared as a W source. Then, a Pt paste was prepared as a Pt source, and the Pt paste was applied to the entire surface of one side of the tungsten member. The Pt paste used in this test was a mixture of 21 vol% Pt powder (average particle size: 0.5 μm), a binder (ethyl cellulose resin), a dispersing agent, and a solvent. The solvent used for the Pt paste was 2,2,4-Trimethyl-1,3-pentanediol 1-Monoisobutyrate. In this test, the Pt paste was dried by performing a drying process at 120°C for 30 minutes, and then debindering process (200°C, 3 hours) was performed in the air.

[0084] Next, a plate-shaped copper member (thickness 0.3 mm, length 20 mm, width 20 mm) was prepared as a Cu source. Then, the paste-coated surface of the tungsten member and the copper member were brought into surface contact, and a 50g alumina block was placed on the tungsten member, so that a pressure of 0.89 kPa was applied to the contact portion between the tungsten member and the copper member. In this state, a firing process was performed with a temperature rise rate of 4°C / min, a maximum firing temperature of 1000°C, and a firing time of 2 hours, to obtain a bonded body (sample 1) in which the tungsten member and the copper member were bonded. Note that N2 gas containing 3% hydrogen (H2) was used as the atmospheric gas during firing.

[0085] 2. Sample Analysis (1) SEM observation and EDX analysis After cutting the bonded body of Sample 1 along the lamination direction, the cut surface was polished by ion milling, and a cross-sectional SEM image of the cut surface was taken. In addition, EDX analysis was performed on the taken cross-sectional SEM image, and element mapping images of tungsten (W), copper (Cu), and platinum (Pt) were obtained. The analysis result at a magnification of 250 times is shown in FIG. 13, the analysis result at a magnification of 1000 times is shown in FIG. 14, the analysis result at a magnification of 10000 times is shown in FIG. 15, and the analysis result at a magnification of 50000 times is shown in FIG. 16. In FIG. 13 to FIG. 16, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, and (d) is an element map of Pt.

[0086] First, as shown in FIG. 13, an alloy layer (Pt-Cu layer) mainly composed of Pt-Cu alloy was observed between the tungsten member and the copper member at a low magnification of 250 times. Although such Pt-Cu alloys usually have low bondability to tungsten members, in the bonded body of Sample 1, the Pt-Cu layer and the tungsten member appeared to be firmly bonded. Then, as shown in FIG. 14, the boundary between the Pt-Cu layer and the tungsten member was observed at a higher magnification (1000 times), and it was found that a layer (W-Pt-Cu layer) in which W, Pt, and Cu were mixed was formed at the boundary between the tungsten member and the Pt-Cu alloy layer. When this W-Pt-Cu layer was further enlarged, a W-Pt-Cu alloy in which W phase was mixed in the Pt-Cu phase matrix was confirmed as shown in FIG. 15 and FIG. 16. From the above analysis results, it was found that a W-Pt-Cu alloy can be produced even when a W source and a Cu source are heated together with a Pt source interposed between them. Furthermore, it was found that the W-Pt-Cu alloy can be used to firmly join tungsten and copper components, which were previously difficult to join.

[0087] (2) Measurement of the number of atoms Next, in this test, in the region where the W-Pt-Cu alloy was formed, five cross-sectional SEM images were obtained at a magnification of 50,000 times as shown in FIG. 16(a). Then, the number of W, Pt, and Cu atoms in each field was measured by EDX composition analysis, and the average value was calculated. As a result, the average number of W atoms in the W-Pt-Cu alloy formed in sample 1 was 34 atm%, and the average number of Pt-Cu atoms was 66 atm%. In addition, the ratio of Pt to Cu in the Pt-Cu alloy was 14.6:85.4.

[0088] (3) Elemental analysis by region In this test, EDX analysis was performed at points 1 to 6 in a 1000x SEM photograph of Sample 1 (see FIG. 17) to measure the atomic ratio (atm%) of W, Pt, and Cu. The measurement results are shown in Table 1 below.

[0089] [Table 1]

[0090] As shown in FIG. 17 and Table 1, it can be seen that point 1 in sample 1 is a tungsten member, point 2 is a W-Pt-Cu layer, points 3 to 5 are Pt-Cu layers, and point 6 is a copper member. And, looking at Table 1, it was found that the Pt / Cu ratio decreases from point 1 to point 6 (the closer to point 1, the higher the Pt / Cu ratio). From this, it can be predicted that in the early stage of sintering, a Pt-W alloy is generated in the region close to the tungsten member (near point 2), and Pt diffuses from the Pt-W alloy toward the copper member (point 6), resulting in the formation of a W-Pt-Cu layer at point 2 adjacent to the tungsten member. Also, in the region away from the tungsten member (points 3 to 4), it can be predicted that a Pt-Cu alloy in which Pt and Cu are mixed is formed, since no Pt-W alloy is formed. In addition, in a metal joint member in which the number of Cu atoms changes sequentially in this way, it is expected that the effect of alleviating thermal stress at the joint portion can be expected.

[0091] (4) Area measurement of W phase In this test, the cross-sectional SEM image of Sample 1 was analyzed to measure the area of ​​the W phase. For the image analysis, image analysis software (ImageJ 1.52a) made by the National Institutes of Health (NIH) was used. Specifically, Figure 15(a) (SEM image at 10,000x magnification) was binarized and inverted to display the W phase in black and the Pt-Cu phase in white. The area of ​​the W phase was measured by counting the black dots present within a 5 μm × 7.5 μm field of view. As a result, a W phase with an area of ​​0.007 μm was found in the matrix of the Pt-Cu phase displayed in white. 2 ~1.02μm 2 The areas of the 85 W layers identified are shown in Table 2 below. In other words, in the W-Pt-Cu alloy in Sample 1, the area of ​​the W phase was 0.007 μm2 or less. 2 ~1.02μm 2 The W phase in the range of about 2.3 points / μm 2 The average area of ​​the W phase in the above field of view was 0.113 μm 2 The maximum area of ​​the W phase was 1.02 μm 2 The minimum value is 0.007 μm 2 It was.

[0092] [Table 2]

[0093] (5) Observation of crystal structure Sample 1 was sliced ​​using FIB-SEM to obtain SEM / EBSD images. The results are shown in FIG. 18. As shown in FIG. 18, in Sample 1, a Pt-Cu alloy was formed between the tungsten member and the copper member, and a W-Pt-Cu alloy was formed at the boundary between the Pt-Cu alloy and the tungsten member. It was confirmed that the W crystal grains were smaller in the region of the tungsten member that contacted the W-Pt-Cu alloy than in other regions. This is presumably because W was supplied from that region to generate the W-Pt-Cu alloy. In addition, an improvement in strength can be expected in the region where the W crystal structure became smaller.

[0094] (6) Elemental mapping In this test, a high angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image (magnification: 50,000 times) of the test piece thinned by FIB-SEM was obtained. An element mapping image was obtained in the HAADF-STEM image, and an EDX spectrum was also obtained. The results of the HAADF-STEM image and the element mapping image are shown in FIG. 19. The EDX spectrum of the entire W-Pt-Cu layer in the obtained HAADF-STEM image is shown in FIG. 20. The EDX spectrum of the W phase in W-Pt-Cu is shown in FIG. 21, and the EDX spectrum of the Pt-Cu phase is shown in FIG. 22.

[0095] First, as shown in FIG. 20, W, Cu, Pt, Mo, Fe, and O elements were mainly confirmed in the entire W-Pt-Cu layer. Then, as shown in FIG. 20 and FIG. 21, W, Mo, Fe, and O elements were mainly confirmed in the W phase. Of these, Mo and Fe elements are thought to be derived from impurities contained in the W plate. In addition, it is possible that Mo was detected from the sample folder. On the other hand, as shown in FIG. 19 and FIG. 22, Cu, Pt, and O elements were mainly confirmed in the Pt-Cu phase. The O element confirmed in both the W phase and the Pt-Cu phase is thought to be derived from oxygen attached in the measurement environment and surface oxidation of the test piece. And, from the image shown in FIG. 19, it was clearly confirmed that the W-Pt-Cu layer is formed of a W-Pt-Cu alloy in which the W phase, which is mainly composed of W, and the Pt-Cu phase, which has a Pt-Cu alloy, are mixed.

[0096] As a result of analyzing FIG. 21, the number of W atoms in the W phase was 84.57 atm%, the number of Cu atoms was 2.56 atm%, and the number of Pt atoms was 0.06 atm%. The W phase also contained 12.81 atm% of molybdenum (Mo), which is an impurity, and it is believed that this was detected as being contained in the sample folder. On the other hand, as a result of analyzing FIG. 22, the number of W atoms in the Pt-Cu phase was 2.31 atm%, the number of Cu atoms was 78.13 atm%, and the number of Pt atoms was 15.59 atm%. The Pt-Cu phase also contained 3.97 atm% of molybdenum (Mo), which is an impurity. It is believed that this Mo was also detected as being contained in the sample folder.

[0097] C. Third Test In this test, ten types of bonded bodies (samples 2 to 11) were produced under different conditions from those in the second test described above. The production conditions for each sample and the analysis performed on each sample are described below.

[0098] (1) Sample 2 In Sample 2, a joint was produced by joining a tungsten member and a copper member under the same conditions as Sample 1, except that the content of Pt powder in the Pt paste was reduced to 10 vol%. SEM observation and EDX analysis were performed on Sample 2 under the same conditions as the second test. The analysis results of Sample 2 at a magnification of 5000 times are shown in FIG. 23, and the analysis results at a magnification of 50000 times are shown in FIG. 24. In addition, in FIG. 23 and FIG. 24, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, and (d) is an element map of Pt. Furthermore, SEM photographs (magnification 50000 times) of the W-Pt-Cu alloy formed in Sample 2 were obtained for five fields of view, and EDX analysis was performed for each field of view to measure the atomic ratio (at%) of W, Pt, and Cu. The measurement results are shown in Table 3 below.

[0099] [Table 3]

[0100] As shown in Figs. 23 and 24, in Sample 2, a ternary two-phase W-Pt-Cu alloy was formed at the joint between the tungsten member and the copper member, similar to Sample 1. Furthermore, calculated from the measurement results in each field of view shown in Table 2, the average value of the abundance ratio of the W phase to the Pt-Cu phase in the W-Pt-Cu layer of Sample 2 was 23.37:76.63. And, the abundance ratio of the Pt element to the Cu element in the Pt-Cu phase was 7.07:92.93. From these results, it was found that the ratio of Pt to Cu in Sample 2 was smaller than that in Sample 1. This is believed to be due to the use of a Pt paste with a lower Pt content than that in Sample 1.

[0101] Next, a line segment X1 with a length of 20 μm was drawn from the upper side (Pt-Cu alloy side) to the lower side (tungsten member side) of FIG. 24(a), and a line analysis was performed to examine the change in element concentration of each element of W, Pt, and Cu on the line segment X1. The results are shown in FIG. 25. The position of 0 μm on the horizontal axis of FIG. 25 corresponds to the upper end of the line segment X1, and the position of 20 μm corresponds to the lower end of the line segment X1. Meanwhile, the vertical axis indicates the characteristic X-ray intensity of each element. Graph (a) in FIG. 25 shows the analysis result of Pt, graph (b) shows the analysis result of W, and graph (c) shows the analysis result of Cu. As shown in FIG. 25, in the region where the Pt-Cu alloy exists (upper side in FIG. 23(a)), Pt element and Cu element are the main components, and W element was hardly confirmed. In the area where the W-Pt-Cu alloy exists (the center part in FIG. 23(a)), W, Pt and Cu elements were confirmed, and in the tungsten member (the lower part in FIG. 23(a)), most of the material was composed of W element, but there was a small amount of Pt element.

[0102] (2) Sample 3 In sample 3, the tungsten member and the copper member were joined under the same conditions as sample 2, except that the temperature when the tungsten member and the copper member were sintered was changed to 800°C. SEM observation and EDX analysis were performed on sample 3 under the same conditions as the second test. The analysis results of sample 3 at a magnification of 5000 times are shown in FIG. 26, the analysis results at a magnification of 50000 times are shown in FIG. 27, and the analysis results at a magnification of 200000 times are shown in FIG. 28. In addition, in FIG. 26 to FIG. 28, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, and (d) is an element map of Pt. From these analysis results, it was confirmed that in sample 3, the region where the W-Pt-Cu alloy exists is thin, and the structure in which the W phase and the Pt-Cu phase are mixed is fine.

[0103] In addition, for sample 3, a quantitative analysis of the numbers of W, Pt, Cu, and O elements was performed based on EDX analysis (FIG. 28) of a cross-sectional SEM image at a magnification of 200,000. In this quantitative analysis, the number of W atoms in the W-Pt-Cu layer was 20.73%, the number of Pt atoms was 5.37 atm%, the number of Cu atoms was 69.11 atm%, and the number of O atoms was 4.79 atm%. As a result of the elemental analysis, no significant difference was observed between sample 2 and sample 3 in the abundance ratio of W, Pt, and Cu elements in the W-Pt-Cu alloy.

[0104] (3) Sample 4 In Sample 4, the tungsten member and the copper member were joined under the same conditions as Sample 2, except that the conditions of the binder removal process after the application of the Pt paste were changed to 160° C. and 30 minutes. SEM observation and EDX analysis were performed on Sample 4 under the same conditions as the second test. The analysis result of Sample 4 at a magnification of 5000 times is shown in FIG. 29, the analysis result of the Pt-Cu layer at a magnification of 50000 times is shown in FIG. 30, the analysis result of the Pt-W layer at a magnification of 50000 times is shown in FIG. 31, the analysis result of the W-Pt-Cu layer at a magnification of 50000 times is shown in FIG. 32, and the analysis result of the tungsten member at a magnification of 50000 times is shown in FIG. 33. In FIG. 29 to FIG. 33, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, and (d) is an element map of Pt. In addition, in sample 4, quantitative analysis of the number of elements of W, Pt, and Cu was performed based on EDX analysis of each cross-sectional SEM image in FIG. 29 to FIG. 33. The analysis results are shown in Table 4. In addition, for sample 4, a line segment X2 with a length of 20 μm was drawn from the upper side (Pt-Cu alloy side) to the lower side (tungsten member side) of FIG. 29(a), and the change in the concentration distribution of each element of W, Pt, and Cu on the line was examined. The results are shown in FIG. 34. The position of 0 μm on the horizontal axis of FIG. 34 corresponds to the upper end of the line segment X2, and the position of 20 μm corresponds to the lower end of the line segment X2. The vertical axis indicates the characteristic X-ray intensity of each element. In FIG. 34, (a) shows the analysis result of Pt, (b) shows the analysis result of W, and (c) shows the analysis result of Cu. As shown in FIG. 34, in the region where the Pt-Cu alloy exists, the presence of Pt and Cu elements was confirmed, and W element was not confirmed. In the area where the W-Pt-Cu alloy was present, W, Pt, and Cu were each confirmed, and the area of ​​the tungsten component was mostly W, with a small amount of Pt present.

[0105] [Table 4]

[0106] In sample 4, the W-Pt-Cu layer was thicker than in the other examples, and a layer mainly composed of Pt-W was present on top of the W-Pt-Cu layer. It is expected that such a thick W-Pt-Cu layer was formed because the temperature of the binder removal treatment was lowered, resulting in a smaller amount of tungsten oxide being produced, and the production of the Pt-W alloy, which is the precursor of the W-Pt-Cu unit, was not inhibited and the layer was formed thick. In addition, as shown in FIG. 29, it was found that a Pt-W layer containing Pt and W was produced at the boundary between the W-Pt-Cu layer and the Pt-Cu layer in sample 4. A part of this Pt-W layer was interrupted, and the W-Pt-Cu layer was present in the interrupted part. From this, it is speculated that in this sample, when the W-Pt-Cu alloy was produced, the Pt-W alloy and Cu were mixed through the interrupted part of the Pt-W layer.

[0107] In addition, in sample 4, sample 1 was thinned using FIB-SEM, and backscattered electron images in a different field of view from that in FIG. 29(a) were obtained and various analyses were performed. First, FIG. 35(a) is a backscattered electron image (5000x) of sample 4, (b) is an enlarged view (20000x) of region α in (a), and (c) is an enlarged view (20000x) of region β in (a). As shown in FIG. 35, in sample 4, a W-Pt-Cu layer was formed on a W plate, a Pt-W layer was formed on the W-Pt-Cu layer, and a Pt-Cu layer was formed on the Pt-W layer. In sample 4, elemental mapping images based on EDX analysis were obtained in each of regions α and β in FIG. 35(a). The result of the elemental mapping image in region α is shown in FIG. 36, and the result of the elemental mapping image in region β is shown in FIG. 37. First, as shown in FIG. 36, it was confirmed that a small amount of Pt-Cu crystal particles existed between Pt-W crystal particles with a particle diameter of about 100 to 500 nm in the Pt-W layer in the region α. ​​The area ratio of the Pt-W crystal particles to the Pt-Cu crystal particles in this Pt-W layer was 98.5:1.5. Moreover, the W phase present at the interface between the W-Pt-Cu layer and the Pt-W layer was formed almost exclusively of tungsten. Moreover, as shown in FIG. 37, the area ratio of the Pt-Cu phase to the W phase in the W-Pt-Cu layer was 52.9:47.1.

[0108] Next, in sample 4, a HAADF-STEM image and an element mapping image of the HAADF-STEM image were also obtained. FIG. 38 shows the results of the HAADF-STEM image and element mapping image of sample 4. FIG. 39 is a graph showing the concentration distribution of Pt, Cu, and W on the line segment X3 in FIG. 38. As shown in FIG. 38 and FIG. 39, in sample 4, a W plate mainly composed of W, a W-Pt-Cu layer having a W phase and a Pt-Cu phase, a Pt-W layer formed of a Pt-W alloy, and a Pt-Cu layer formed of a Pt-Cu alloy were formed. The abundance ratio of the metal elements in each layer was as shown in Table 5 below.

[0109] [Table 5]

[0110] Furthermore, FIG. 40 shows the results of HAADF-STEM images and element mapping images at the interface between the W plate of sample 4, the W phase of the W-Pt-Cu layer, and the Pt-Cu phase of the W-Pt-Cu layer. Also, FIG. 41 is a graph showing the concentration distribution of Pt, Cu, and W on the line segment X4 in FIG. 40, and FIG. 42 is a graph showing the concentration distribution of O and Fe on the line segment X4. First, as shown in FIG. 40 and FIG. 41, the W plate contains almost no Pt element or Cu element, and the Pt-Cu phase of the W-Pt-Cu layer contains almost no W element. From this, it is understood that there is almost no diffusion of metal elements at the interface between the Pt-Cu phase of the W-Pt-Cu layer and the W plate. Also, as shown in FIG. 40 and FIG. 42, the presence of a small amount of iron (Fe) element was confirmed in the W plate. Also, it is presumed that the oxygen (O) element is due to measurement noise. These Fe and O elements were present in all regions, and no clear uneven distribution was confirmed at the interface between the Pt-Cu phase and the W plate in the W-Pt-Cu layer.

[0111] In addition, in sample 4, electron beam diffraction was performed in each of the regions α to δ in FIG. 38. The results are shown in FIG. 43. FIG. 43(a) is an image showing the results of electron beam diffraction in the region α (W plate). From the electron beam diffraction results, the element present in the region α (W plate) was identified as W. Next, FIG. 43(b) is an image showing the results of electron beam diffraction in the region β (W-Pt-Cu layer). From the electron beam diffraction results, W phase and Pt-Cu phase were confirmed in the region β (W-Pt-Cu layer). Furthermore, it was found that at least Cu3Pt exists in the Pt-Cu phase in the W-Pt-Cu layer. Also, FIG. 43(c) is an image showing the results of electron beam diffraction in the region γ (Pt-W layer). In the Pt-W layer, in addition to the Pt-W alloy, the Pt-Cu alloy was also confirmed. The Pt-W layer contained at least Pt2W as a Pt-W alloy, and at least Cu3Pt as a Pt-Cu alloy. Figure 43(d) is an image showing the results of electron beam diffraction in region δ (Pt-Cu layer). The Pt-Cu layer contained at least Cu3Pt as a Pt-Cu alloy.

[0112] Next, as shown in FIG. 40, in Sample 4, HAADF-STEM images and element mapping images were obtained at the interface between the W plate and the W-Pt-Cu layer. In addition, in Sample 4, HAADF-STEM images and element mapping images were obtained at each of the W plate, the Pt-W layer, and the Pt-Cu layer. The results are shown in FIG. 44 to FIG. 46. As shown in FIG. 40 and FIG. 44 to FIG. 46, in Sample 4, a Pt-Cu phase having Pt and Cu was confirmed in each of the regions of the W plate, the W-Pt-Cu layer, the Pt-W layer, and the Pt-Cu layer. The EDX spectrum of the Pt-Cu phase in each of these regions is shown in FIG. 47 to FIG. 50, and the element ratio calculated based on the EDX spectrum is shown in Table 6. As shown in FIG. 47 to FIG. 50 and Table 6, there was no significant difference in the element ratio of the Pt-Cu phase present in each layer.

[0113] [Table 6]

[0114] As a result of the above analysis, in Sample 4, a W-Pt-Cu alloy was formed between the Pt-W layer and the W plate. From this, it is considered that after the Pt-W alloy was generated by applying Pt paste to the W plate and heating it, a component containing Cu penetrated into the Pt-W alloy, and the Pt in the Pt-W alloy moved (diffused) into Cu, thereby generating the W-Pt-Cu alloy. Furthermore, as shown in FIG. 44, in Sample 4, Cu also penetrated into the W plate. This is also understood to suggest the generation process in which Cu penetrates into the Pt-W alloy.

[0115] (4) Sample 5 In Sample 5, the tungsten member and the copper member were joined under the same conditions as Sample 2, except that the conditions of the binder removal treatment after the application of the Pt paste were changed to 450°C and 30 minutes. SEM observation and EDX analysis were performed on Sample 5 under the same conditions as the second test. The analysis results of Sample 5 at a magnification of 5000 times are shown in FIG. 51, and the analysis results of the W-Pt-Cu alloy at a magnification of 50000 times are shown in FIG. 52. In addition, in FIG. 51 and FIG. 52, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, and (d) is an element map of Pt. As a result of this analysis, it was confirmed that the W-Pt-Cu layer in Sample 5 was thinner than those in Samples 1, 2, and 4, and the distribution of the W-Pt-Cu alloy on the W plate was patchy. This is presumably because the temperature of the binder removal treatment was increased, which resulted in the formation of tungsten oxide on the surface of the W plate, which inhibited the reaction between the W member and Pt, and inhibited the formation of a Pt-W alloy. In addition, for sample 5, a quantitative analysis of the numbers of W elements, Pt elements, and Cu elements in the W-Pt-Cu alloy was performed based on the EDX analysis in FIG. 52. As a result of this quantitative analysis, the number of W atoms in the W-Pt-Cu layer was 31.06%, the number of Pt atoms was 2.03 atm%, and the number of Cu atoms was 66.91 atm%. As a result of this elemental analysis, it was found that the abundance ratio of Pt elements in the W-Pt-Cu alloy of sample 5 was lower than that of samples 2 to 4.

[0116] (5) Sample 6 In Sample 6, instead of a plate-shaped copper member, a Cu paste was used as the Cu source. Specifically, a Pt paste having the same composition as Sample 2 was applied to the surface of a tungsten member having the same dimensions as Sample 1. Then, drying and debinding were performed under the same conditions as Sample 4. Then, Cu paste was applied to the surface to which the Pt paste was applied, followed by drying (120°C, 30 minutes) and heating. The heating conditions were set to the same as Sample 1. The Cu paste used in this sample was a mixture of Cu powder with an average particle size of 0.5 μm, glass powder, ethyl cellulose resin, a dispersing agent, and a solvent. SEM observation and EDX analysis were performed on Sample 6 under the same conditions as the second test. The analysis results of Sample 6 at a magnification of 5000 times are shown in FIG. 53, and the analysis results of the W-Pt-Cu alloy at a magnification of 50000 times are shown in FIG. 54. In addition, in Fig. 53 and Fig. 54, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, and (d) is an element map of Pt. As a result of such analysis, the generation of W-Pt-Cu alloy was confirmed in Sample 6 as in the other samples. From this, it was found that Cu paste can be used as the Cu source even in the embodiment in which the W source, the Pt source, and the Cu source are simultaneously heat-treated. In addition, in Sample 6, a quantitative analysis of the element numbers of W elements, Pt elements, and Cu elements in the W-Pt-Cu alloy was performed based on the EDX analysis in Fig. 54. As a result of such quantitative analysis, the number of W atoms in the W-Pt-Cu layer of Sample 6 was 40.16%, the number of Pt atoms was 2.27 atm%, and the number of Cu atoms was 57.57 atm%.

[0117] (6) Sample 7 In sample 7, we investigated whether a W-Pt-Cu alloy would be generated when an intermediate metal member (Pt film) was interposed between the W-Pt alloy and the Cu source. Specifically, a thick layer of Pt paste with the same composition as sample 2 was applied to the surface of a tungsten member with the same dimensions as sample 1. Then, after drying at 120°C for 30 minutes, the binder was removed by heating in the air (heating rate: 10°C / min, maximum temperature: 160°C, heating time: 0.5 h). Then, a firing process (heating rate: 4°C / min, maximum temperature: 1000°C, firing time: 2 hours) was performed in an N2-H2 (3%) atmosphere. Then, the sample was cooled to room temperature, and it was confirmed that a Pt fired film was generated on the surface of the W plate. Next, the same Cu paste as sample 6 was applied to the surface of this Pt fired film and dried at 120°C for 30 minutes. Then, the sample was subjected to a firing process (heating temperature: 4°C / min, maximum temperature: 1000°C, firing time: 2 hours) in a N2-H2 (3%) atmosphere. After the sample was cooled to room temperature, the cross section was polished by ion milling, and SEM observation and EDX analysis were performed.

[0118] The analysis results of Sample 7 at a magnification of 5000 times are shown in FIG. 55. The analysis results of Sample 7 at a magnification of 50000 times are shown in FIG. 56 to FIG. 59 for each of the Pt-W layer, the W-Pt-Cu layer, the W plate, and the interface between the W plate and the W-Pt-Cu layer. In FIG. 55 to FIG. 59, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, and (d) is an element map of Pt. As shown in FIG. 55 to FIG. 59, it was confirmed that the W-Pt-Cu alloy was generated in Sample 7 as in Samples 2 to 6. From this, it was found that in order to generate the W-Pt-Cu alloy, it is not necessary to directly contact the W-Pt alloy with the Cu source, and an intermediate metal member (Pt film) may be interposed between the W-Pt alloy and the Cu source.

[0119] For Sample 7, a quantitative analysis of the number of W, Pt, and Cu elements in the W-Pt-Cu alloy was performed based on the EDX analysis of each of Figures 55 to 59. Table 7 shows the analysis results at 5000x magnification (Figure 55) and the results of the quantitative analysis of the number of elements in each of the Pt-W layer (Figure 56), W-Pt-Cu layer (Figure 57), W plate (Figure 58), and the interface between the W plate and the W-Pt-Cu layer (Figure 59).

[0120] [Table 7]

[0121] (7) Sample 8 In sample 8, the shapes of the Pt-W alloy produced in the Pt-W alloy production process and the W-Pt-Cu alloy produced in the W-Pt-Cu alloy production process were compared. Specifically, a thin layer of Pt paste with the same composition as sample 2 was applied to the surface of a W plate with the same dimensions as sample 1. Then, after drying at 120°C for 30 minutes, the binder was removed by heating in the air (heating rate: 10°C / min, maximum temperature: 160°C, heating time: 0.5h). Then, a firing process (heating rate: 4°C / min, maximum temperature: 1000°C, firing time: 2 hours) was performed in an N2-H2 (3%) atmosphere. Then, the sample was cooled to room temperature, and it was confirmed that the W-Pt alloy was produced on the surface of the W plate. The surface of the W-Pt alloy produced in this sample was a rough surface with fine irregularities. Next, in this sample, a coated area was prepared by applying Cu paste (Cu source) to the surface of the W-Pt alloy, and an uncoated area was prepared by not applying Cu paste. The Cu paste used was the same as that used in sample 6. The Cu paste in the coated area was dried at 120°C for 30 minutes, and then sintered in a N2-H2 (3%) atmosphere (temperature rise: 4°C / min, maximum temperature: 1000°C, sintering time: 2 hours). The sample was then cooled to room temperature, and the cross section was polished by ion milling, and SEM observation and EDX analysis were performed.

[0122] The analysis results of the uncoated area of ​​Sample 8 are shown in Figures 60 and 61. Meanwhile, the analysis results of the coated area are shown in Figures 62 to 65. First, as shown in Figure 60, a W-Pt alloy having fine irregularities was formed on the surface of the W plate in the uncoated area. Meanwhile, as shown in Figures 62 to 65, a W-Pt-Cu alloy was formed between the W plate and the Pt-Cu layer in the coated area. And, the W-Pt-Cu alloy in Sample 8 had fine irregularities formed on the surface (interface on the Pt-Cu layer side) like the W-Pt alloy in the uncoated area. From this, it was found that the shape of the Pt-W alloy generated in the Pt-W alloy generation process was reflected in the shape of the W-Pt-Cu alloy after the W-Pt-Cu alloy generation process.

[0123] (8) Sample 9 In Sample 9, Cu paste was applied to the surface of a plate-shaped tungsten member, and then dried and fired. Specifically, Cu paste of the same composition as Sample 6 was applied to the surface of a tungsten member of the same dimensions as Sample 1. Then, a drying process was performed at 120°C for 30 minutes to dry the Cu paste, and then a heat treatment was performed in air at 400°C for 1 hour. Then, a firing process was performed with a firing rate of 5°C / min, a maximum firing temperature of 1000°C, and a firing time of 30 minutes. SEM observation and EDX analysis were performed on Sample 9 under the same conditions as the second test. The analysis results of Sample 9 at a magnification of 250 times are shown in FIG. 66, the analysis results at a magnification of 1000 times are shown in FIG. 67, the analysis results at a magnification of 5000 times are shown in FIG. 68, and the analysis results at a magnification of 50000 times are shown in FIG. 69. In addition, (a) in Figures 66 to 69 is a cross-sectional SEM image, (b) is an element map of O (oxygen), (c) is an element map of Cu, and (d) is an element map of W. Even from these analyses, an alloy material in which W and Cu are mixed was not formed. In other words, it was found that even if Cu and W are brought into contact with each other and heat treated in a state in which Pt is not present (a state in which a W-Pt alloy is not formed), an alloy material in which W and Cu are mixed is not formed.

[0124] (9) Sample 10 In Sample 10, Pt paste was applied to the surface of a plate-shaped tungsten member, and then dried and fired. Specifically, Pt paste with the same composition as Sample 1 was applied to the surface of a tungsten member with the same dimensions as Sample 1. Then, the Pt paste was dried by drying at 120°C for 30 minutes, and then heated in air at 160°C for 0.5 hours. Then, a firing process was performed with a firing rate of 3°C / min, a maximum firing temperature of 1300°C, and a firing time of 10 minutes. SEM observation and EDX analysis were performed on Sample 10 under the same conditions as the second test. The analysis results of Sample 10 at a magnification of 5000 times are shown in Figure 70. Note that (a) in Figure 70 is a cross-sectional SEM image, (c) is an element map of W, and (d) is an element map of Pt. As a result of these analyses, it was confirmed that an alloy containing Pt and W (Pt-W alloy) was generated by heating the Pt source and W source in contact with each other as in this sample. However, in this sample, a two-phase alloy like that in Samples 1 to 8 was not produced.

[0125] (10) Sample 11 In sample 11, Pt-Cu paste was applied to the surface of a plate-shaped tungsten member, and dried and fired. Specifically, Pt-Cu paste, in which Pt particles and Cu particles were uniformly dispersed, was applied to the surface of a tungsten member having the same dimensions as sample 1. Then, after drying the paste at 120°C for 30 minutes, a first heating process was performed in air at 160°C for 0.5 hours, and then a second heating process was performed in N2 gas containing 3% H2 gas, with a heating rate of 10°C / min, a maximum heating temperature of 400°C, and a heating time of 1 hour. Then, a heating process was performed with a heating rate of 5°C / min, a maximum firing temperature of 1000°C, and a firing time of 30 minutes. SEM observation was performed on sample 11 under the same conditions as the second test. The analysis result of sample 11 at a magnification of 5000 times is shown in FIG. 71, and the analysis result at a magnification of 50000 times is shown in FIG. 72. As a result of these analyses, when the Pt source and the Cu source were mixed as in this sample, the W-Pt-Cu alloy was not generated, and only the unreacted W member and the Pt-Cu alloy formed on the surface of the W member were confirmed, even though the W member, Pt source, and Cu source were present. And, such W member and the Pt-Cu alloy were not properly joined. The cause of such a result is presumed to be as follows. In this sample, the reaction between the mixed Pt source and the Cu source occurred preferentially, and the Pt-W alloy was not generated. And, since the Pt-Cu alloy generated by the reaction of the Pt source and the Cu source has low reactivity with the W member, the W-Pt-Cu alloy as in samples 1 to 6 was not formed. From this, it was found that in order to generate the W-Pt-Cu alloy, it is necessary to generate a Pt-W alloy as a precursor and move Pt from the Pt-W alloy to Cu.

[0126] D. Fourth Test In this test, a W-Pt-Cu alloy having a Pt-Cu phase containing a metal element (a third metal element) other than Cu and Pt was produced. The specific production procedure is described below.

[0127] Here, first, Pt paste was applied to a W plate with a thickness of 0.3 mm x 7.5 mm x 7.5 mm. The Pt paste was prepared by kneading Pt powder with an average particle size of 0.5 μm, a binder (ethyl cellulose resin), a dispersing agent, and a solvent (2,2,4-Trimethyl-1,3-pentanediol 1-Monoisobutyrate). Then, the W plate on which the Pt paste was applied was dried (120°C, 30 minutes), and then debindered (in air, 160°C, 0.5 hours). Then, a heat treatment was performed in a reducing atmosphere (N2-H2 (3%) atmosphere) to generate a Pt-W alloy (Pt2W) on the surface of the W plate. In the heat treatment, the temperature rise rate was set to 4°C / min, and the maximum temperature (1000°C) was reached and then held for 2 hours.

[0128] Next, Au paste was applied onto the Pt-W alloy on the W plate surface, and then dried (120°C, 30 minutes). The Au paste was prepared by kneading Au powder with an average particle size of 0.5 μm, a binder (ethyl cellulose), a dispersing agent, and a solvent (terpineol). Cu paste was applied onto the dried Au paste, and then dried (120°C, 30 minutes). The Cu paste was the same as the paste used in the preparation of the analysis sample A-2 in the first test. Sample 12 was prepared by performing a heat treatment in a reducing atmosphere (N2-H2 (3%) atmosphere). In the heat treatment, the temperature rise rate was set to 4°C / min, and the maximum temperature (1000°C) was reached and then held for 2 hours.

[0129] The cross section of the fabricated sample 12 was CP polished and subjected to SEM-EDX analysis. The results are shown in Figs. 73 and 74. The magnification of Fig. 73 is 5000 times, and the magnification of Fig. 74 is 50000 times. In Figs. 73 and 74, (a) is a cross-sectional SEM image, (b) is an element map of W, (c) is an element map of Cu, (d) is an element map of Pt, and (e) is an element map of Au. The atomic concentration of Cu measured by SEM-EDX analysis was 65.64%, the atomic concentration of W was 24.50%, the atomic concentration of Pt was 1.23%, and the atomic concentration of Au was 8.62%.

[0130] As a result of the analysis, it was confirmed that a W-Pt-Cu alloy containing a mixture of W and Pt-Cu phases was also generated in Sample 12. However, it was found that the Pt-Cu phase of the W-Pt-Cu alloy generated in this sample contained Au in addition to Pt and Cu (see Figures 73(e) and 74(e)). From this result, it was found that when a third element is contained in the Cu source, as in this test, the third element diffuses into the Pt-Cu phase together with Cu and Pt.

[0131] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0132] 10 Alloy material 12 W phase 14 Pt-Cu phase 20 First member 30 Second member 100 zygote

Claims

1. An alloy material characterized by the mixture of a W phase containing tungsten (W) as a main component and a Pt--Cu phase containing platinum (Pt) and copper (Cu).

2. 2. The alloy material according to claim 1, wherein a plurality of said W phases are present in a matrix consisting of said Pt--Cu phase.

3. In SEM observation, the area was 0.001 μm 2 ~1μm 2 W phase is 0.2 places / μm 2 3. The alloy material according to claim 1, further comprising a W phase region that exists at a density of at least 10 μm, and the W phase region exists in a predetermined direction to a length of at least 10 μm.

4. In the W phase region, the area is 0.001 μm 2 ~0.1μm 2 W phase is 0.2 places / μm 2 4. The alloy material of claim 3, wherein said alloy material is present at a density equal to or greater than 1000 nm.

5. The alloy material according to any one of claims 1 to 4, characterized in that, when the total number of metal elements present in the W phase is 100 atm %, the number of tungsten atoms present in the W phase is 75 atm % or more.

6. A joined body, comprising a first member containing tungsten and a second member joined via the alloy material according to any one of claims 1 to 5.

7. 7. The joint body according to claim 6, wherein the first member includes at least one selected from the group consisting of tungsten, tungsten nitride, tungsten carbide, tungsten carbonitride, a copper-tungsten composite material, and a silver-tungsten composite material.

8. 8. The joint body according to claim 6, wherein the second member includes at least one selected from the group consisting of copper, platinum, a platinum-copper alloy, and a platinum-tungsten alloy.

9. A method for producing the alloy material according to any one of claims 1 to 5, comprising the steps of: A method for producing an alloy material, comprising transferring platinum (Pt) of a Pt-W alloy containing platinum (Pt) and tungsten (W) to a copper (Cu) source containing copper (Cu).

10. The method for producing an alloy material according to claim 9, wherein the Pt-W alloy is an intermetallic compound.

11. The Pt-W alloy is Pt 2 The method for producing the alloy material according to claim 10, wherein W is W.

12. The method for producing an alloy material according to any one of claims 9 to 11, further comprising contacting the Pt-W alloy with the Cu source.

13. The method for producing an alloy material according to claim 12, further comprising heating the contacted Pt-W alloy and Cu source.

14. a Pt-W alloy generating step of generating a Pt-W alloy by performing a heat treatment in a state where a Pt source containing platinum (Pt) and a W source containing tungsten (W) are in contact with each other; a W—Pt—Cu alloy generating step of transferring platinum (Pt) in the Pt—W alloy to the Cu source by performing a heat treatment while the Pt—W alloy is in contact with the Cu source to generate a W—Pt—Cu alloy; The method of claim 13 , comprising:

15. The method for producing an alloy material according to claim 14, wherein the heating temperature in the Pt-W alloy producing step is 800° C. or higher and 1200° C. or lower.

16. The method for producing an alloy material according to claim 14 or 15, wherein the heating time in the Pt-W alloy producing step is 0.5 hours or more and 3 hours or less.

17. The method for producing an alloy material according to any one of claims 14 to 16, wherein the heating temperature in the W-Pt-Cu alloy producing step is 800°C or higher and 1200°C or lower.

18. The method for producing an alloy material according to any one of claims 14 to 17, wherein the heating time in the W-Pt-Cu alloy producing step is 0.5 hours or more and 3 hours or less.

19. 10. The method for producing an alloy material according to claim 9, wherein a heat treatment is performed in a state in which a Pt source containing platinum (Pt) is interposed between a W source containing tungsten (W) and the Cu source, thereby generating a Pt-W alloy at the boundary between the W source and the Pt source, and transferring platinum (Pt) in the Pt-W alloy to the Cu to generate a W-Pt-Cu alloy.

20. The method for producing an alloy material according to claim 19, wherein the temperature of the heat treatment is 800° C. or more and 1200° C. or less.

21. The method for producing an alloy material according to claim 19 or 20, wherein the heat treatment time is from 0.5 hours to 3 hours.

22. In the heat treatment, the W source and the Cu source were sandwiched between 0.5 g / mm 2 5g / mm or more 2 The method for producing an alloy material according to any one of claims 19 to 21, wherein the pressure is:

23. The method for producing an alloy material according to any one of claims 9 to 11, further comprising interposing an intermediate metal member between the Pt-W alloy and the Cu source.

24. The method for producing an alloy material according to claim 23, further comprising heating the contacted Pt-W alloy, intermediate metal member, and Cu source.

25. The method for producing an alloy material according to claim 23 or 24, wherein the intermediate metal part contains at least Pt.

Citation Information

Patent Citations

  • Heterojunction metal probe, its manufacture and probe card using heterojunction metal probe

    JP2000187043A

  • Electrocatalyst containing platinum and tungsten

    JP2009518814A

  • Laminate, heat sink and method of manufacturing laminate

    JP2013180479A

  • Process of bonding copper and tungsten

    US5988488A

  • Device for treating waste water

    JP1978085951A